Energy ray curable resin film, energy ray curable resin film composite sheet, and method for manufacturing a semiconductor device.
Patent Information
- Application Number
- JP2025058700
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0008】 本発明によれば、突状電極付き部材への貼付時に気泡発生を抑制することのできるエネルギー線硬化性樹脂フィルム及び該エネルギー線硬化性樹脂フィルムを有するエネルギー線硬化性樹脂フィルム複合シート、及びこれらを用いた半導体装置の製造方法を提供することが可能となる。
Smart Images

Figure 2026166013000001_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to an energy-ray curable resin film, an energy-ray curable resin film composite sheet, and a method for manufacturing a semiconductor device. [Background technology]
[0002] In recent years, with the miniaturization and thinning of electronic devices, there has been an increasing demand for thinner and smaller semiconductor packages. Therefore, as a mounting method for semiconductor elements, a flip-chip mounting method has been proposed, replacing the conventional wire bonding method which uses metal wires for connection. This method involves forming protruding electrodes, such as bumps, on the chip's electrodes, and directly connecting the substrate electrodes to the chip's electrodes via these protruding electrodes.
[0003] Incidentally, on wafers with protruding electrodes, a protective film is sometimes provided on the surface where the protruding electrodes are formed, for the purpose of protecting the junction between the protruding electrodes and the semiconductor wafer (also called the "bump neck" if the protruding electrodes are bumps). For example, in Patent Document 1, a laminate in which a first substrate, an adhesion layer, a buffer layer, and a thermosetting resin film are stacked in this order is pressed and attached to the bump-forming surface of a semiconductor wafer having bumps, with the thermosetting resin film as the bonding surface, and then the thermosetting resin film is heated and cured to form a protective film. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] International Publication No. 2021 / 172431 [Overview of the project] [Problems that the invention aims to solve]
[0005] However, since thermosetting resin films require heating at high temperatures for a long time to cure, from the viewpoint of work efficiency, it is preferable to use energy ray curable resin films that do not require heating at high temperatures and can be cured in a short time. In the process of attaching a resin film to the surface of the protruding electrodes of a wafer with protruding electrodes, air bubbles may get trapped, particularly in the gaps between the protruding electrodes. Such air bubbles may burst when exposed to high temperatures during reliability evaluations performed in later processes, potentially leading to a decrease in the reliability of the package. Therefore, it is preferable that they not remain. However, when using thermosetting resin film, even if air bubbles get trapped during application, they will escape when heated. In contrast, when using energy ray curing resin film, as mentioned above, it is not heated to a high temperature, so if air bubbles get trapped during application, they may remain. Therefore, there is a need for an energy-ray curable resin film that can suppress the generation of air bubbles during application.
[0006] The present invention aims to provide an energy-ray curable resin film that can suppress the generation of air bubbles when attached to a member with protruding electrodes, an energy-ray curable resin film composite sheet having the energy-ray curable resin film, and a method for manufacturing a semiconductor device using the same. [Means for solving the problem]
[0007] According to the present invention, the following [1] to [5] are provided. [1] An energy-ray curable resin film for forming a protective film on the protruding electrode forming surface of a member with a protruding electrode, comprising a polymer component (A) which is a polymer with a weight-average molecular weight of 5,000 or more, and a compound component (B) which is a compound having an energy-ray curable group and a weight-average molecular weight of less than 5,000, An energy ray-curable resin film, wherein the polymer component (A) comprises an acrylic resin (A1) having a weight average molecular weight (Mw) of 5,000 to 250,000, and the compound component (B) comprises a radically polymerizable energy ray-curable compound (B1) having a weight average molecular weight of less than 5,000. [2] The energy ray-curable resin film according to [1], further comprising a photopolymerization initiator (C). [3] The energy ray-curable resin film according to [1] or [2], wherein the radically polymerizable energy ray-curable compound (B1) comprises an acrylate-based compound. [4] An energy ray-curable resin film composite sheet comprising a support sheet and the energy ray-curable resin film according to any one of [1] to [3]. [5] A method for manufacturing a semiconductor device, comprising the step of forming a protective film on the protruding electrode-forming surface of a member with protruding electrodes using the energy ray-curable resin film according to any one of [1] to [3]. [Advantageous Effects of the Invention]
[0008] According to the present invention, it is possible to provide an energy ray-curable resin film capable of suppressing bubble generation when being attached to a member with protruding electrodes, an energy ray-curable resin film composite sheet having the energy ray-curable resin film, and a method for manufacturing a semiconductor device using the same. [Brief Description of the Drawings]
[0009] [Figure 1] It is a schematic cross-sectional view showing an example of the embodiment of the composite sheet of the present embodiment. [Figure 2] It is a schematic cross-sectional view showing another example of the embodiment of the composite sheet of the present embodiment. [Figure 3] It is a schematic cross-sectional view showing still another example of the embodiment of the composite sheet of the present embodiment. [Figure 4]This is a schematic cross-sectional view showing an example of Step 1 in the method for manufacturing a semiconductor device according to the present embodiment. [Figure 5] This is a schematic cross-sectional view showing an example of Step 2 in the method for manufacturing a semiconductor device according to the present embodiment. [Figure 6] This is a schematic cross-sectional view showing an example of Step 3 in the method for manufacturing a semiconductor device according to the present embodiment. [Figure 7] This is a schematic cross-sectional view showing an example of Step 4 in the method for manufacturing a semiconductor device according to the present embodiment. [Mode for Carrying Out the Invention]
[0010] In the present specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are values in terms of standard polystyrene measured by a gel permeation chromatography (GPC) method, and specifically are values measured based on the methods described in the Examples.
[0011] In the present specification, the glass transition temperature (Tg) can be determined by calculation using the Fox equation. For example, the Tg of an acrylic resin can be determined by calculation using the Fox equation shown below. 1 / Tg=(W1 / Tg1)+(W2 / Tg2)+…+(Wm / Tgm) (wherein Tg is the glass transition temperature of the acrylic resin, Tg1, Tg2, ... Tgm are the glass transition temperatures of homopolymers of the respective monomers that are raw materials of the acrylic resin, and W1, W2, ... Wm are the mass fractions of the respective monomers, provided that W1+W2+...+Wm=1.) As the glass transition temperature of the homopolymer of each monomer in the above Fox equation, values described in Polymer Data Handbook, Pressure Sensitive Adhesive Handbook, or Polymer Handbook can be used. For example, the Tg of methyl acrylate homopolymer is 10°C, the Tg of 2-hydroxyethyl acrylate homopolymer is -15°C, the Tg of 2-ethylhexyl acrylate is -70°C, and the Tg of 2-ethylhexyl methacrylate is -10°C.
[0012] In this specification, the lower and upper limits described in steps for a preferred numerical range (e.g., range of content, etc.) can be combined independently. For example, from the description "preferably 10 to 90, more preferably 30 to 60", the "preferred lower limit (10)" and the "more preferred upper limit (60)" can be combined to arrive at "10 to 60".
[0013] In this specification, "energy beam" means an electromagnetic wave or charged particle beam that has an energy quantum. Examples of energy beams include ultraviolet rays, radiation, and electron beams. Ultraviolet rays can be irradiated using electrodeless lamps, high-pressure mercury lamps, metal halide lamps, xenon lamps, black lights, LED lamps, etc. Electron beams can be irradiated using those generated by electron accelerators, etc.
[0014] In this specification, "energy ray curability" means the property of hardening by irradiation with energy rays. In this specification, "thermosetting property" means the property of hardening by heating.
[0015] In this specification, for example, "(meth)acrylic acid" refers to both "acrylic acid" and "methacrylic acid," and the same applies to other similar terms.
[0016] In this specification, "protruding electrode" refers to a protruding electrode of a shape commonly used on the circuit formation surface of semiconductor wafers, semiconductor chips, etc., such as ball bumps and pillar electrodes.
[0017] In this specification, the "thickness" of an object means the total thickness of the object as a whole. For example, if the object consists of multiple layers, it means the total thickness of all the layers that make up the object. In this specification, unless otherwise specified, the "thickness" of an object refers to the average value of the thickness measured at five randomly selected locations on the object, and can be obtained using a constant-pressure thickness measuring instrument in accordance with JIS K 7130:1999.
[0018] In this specification, "solid content" or "active ingredient" refers to the components of the composition in question, excluding diluting solvents such as water and organic solvents.
[0019] In this specification, "before curing" means the state of a thermosetting or energy ray curing resin film before it is subjected to thermosetting or energy ray curing treatment. For example, a thermosetting or energy ray curing resin composition described later that has been dried (drying temperature 70-130°C, drying time 10 seconds-5 minutes) is also included in the "before curing" state of a thermosetting or energy ray curing resin film.
[0020] In this specification, "after curing" means the state after a thermosetting or energy ray curing treatment has been performed on a thermosetting or energy ray curing resin film. The conditions for energy ray hardening treatment are: energy ray illuminance: 60-320 mW / cm² 2 Integrated luminous energy: 100-1000 mJ / cm² 2 It is preferable that the conditions are as described below for measuring the storage modulus (E'2) at 25°C after curing. The conditions for the thermosetting treatment may be a temperature of 90°C to 200°C and a time of 1 to 5 hours, or the same conditions used for measuring the storage modulus (E'2) at 25°C after curing, as described in the examples below.
[0021] The mechanism of action described herein is speculative and does not limit the mechanism by which the present invention achieves its effects.
[0022] In order to make the features of the present invention easier to understand, the drawings may show enlarged versions of key parts for convenience, and the dimensional ratios of each component may not be the same as in reality.
[0023] [Energy ray curable resin film] The energy-ray curable resin film of this embodiment is an energy-ray curable resin film for forming a protective film on the protruding electrode forming surface of a member with a protruding electrode, comprising a polymer component (A) which is a polymer with a weight-average molecular weight of 5,000 or more, and a compound component (B) which is a compound having an energy-ray curable group and a weight-average molecular weight of less than 5,000, wherein the polymer component (A) comprises an acrylic resin (A1) with a weight-average molecular weight (Mw) of 5,000 or more and the compound component (B) comprises a radical polymerizable energy-ray curable compound (B1) with a weight-average molecular weight of less than 5,000. The inventors diligently conducted research to solve the above problems. As a result, they found that the above problems can be solved by further including an acrylic resin film (A1) as a polymer component (A) having a weight-average molecular weight (Mw) of 5,000 or more and 250,000 or less, in an energy-ray curable resin film for forming a protective film on the protruding electrode surface of a member with a protruding electrode containing a radical polymerizable energy-ray curable compound (B1) having a weight-average molecular weight (B1) of less than 5,000. The reason is not entirely clear, but for example, it could be as follows: The energy-ray curable resin film of this embodiment contains an acrylic resin (A1) with a relatively small weight-average molecular weight, which allows the storage modulus of the film before curing to be lowered. As a result, the film deforms easily when applied, and when applied, the film adheres closely to the shape of the protruding electrodes on the surface of the member, making it easier to expel the air present in the gaps between the protruding electrodes from the system, thus allowing the film to be applied without bubbles. Hereinafter, the energy-ray curable resin film will also be referred to as "energy-ray curable resin film (x)".
[0024] <Composition of energy ray curable resin film (x)> The energy-ray curable resin film (x) contains a polymer component (A) and a compound component (B). The energy-ray curable resin film (x) is formed, for example, from an energy-ray curable resin composition (x1) containing a polymer component (A) and a compound component (B). Polymer component (A) is a polymer with a weight-average molecular weight of 5,000 or more. Compound component (B) is a compound having an energy-ray curable group and a weight-average molecular weight of less than 5,000.
[0025] (Polymer component (A)) The energy-ray curable resin film (x) and the energy-ray curable resin composition (x1) contain a polymer component (A). As stated above, in this application, polymer component (A) refers to a polymer with a weight-average molecular weight of 5,000 or more. Polymer component (A) is a polymer compound used to impart film-forming properties, flexibility, and other characteristics to energy-ray curable resin films. Polymer component (A) may be used alone or in combination of two or more types. When using two or more types of polymer component (A) in combination, the combination and ratio can be arbitrarily selected. Examples of polymer components (A) include acrylic resins, polyarylate resins, acetal resins, polyesters, urethane resins (resins having urethane bonds), acrylic urethane resins, silicone resins (resins having siloxane bonds), rubber resins (resins having a rubber structure), phenoxy resins, and thermosetting polyimides. Among these, the energy-ray curable resin film (x) of this embodiment contains an acrylic resin (A1) having a weight-average molecular weight (Mw) of 5,000 or more and 250,000 or less. It is also preferable to further include a urethane resin (A2) as the polymer component (A). In the following, acrylic resins (A1) with a weight-average molecular weight (Mw) of 5,000 or more and 250,000 or less will also be simply referred to as acrylic resins (A1).
[0026] The weight-average molecular weight (Mw) of polymer component (A) is preferably 5,000 or more and less than 400,000, more preferably 5,000 or more and 300,000 or less, even more preferably 5,000 or more and 250,000 or less, even more preferably 5,000 or more and 225,000 or less, even more preferably 7,000 or more and less than 200,000, even more preferably 8,000 or more and 100,000 or less, and even more preferably 10,000 or more and 50,000 or less. Furthermore, if polymer component (A) contains multiple components, the weight-average molecular weight (Mw) of each component contained in polymer component (A) shall satisfy the above range. By having a weight-average molecular weight of polymer component (A) above the lower limit mentioned above, the dimensional stability (stable over time during storage) of the energy-ray-curable resin film (x) can be easily improved, and leakage during standing can be suppressed. Furthermore, by having a weight-average molecular weight of polymer component (A) below the upper limit mentioned above, the adhesion of the film to the protruding electrode can be improved, and the generation of air bubbles during application can be easily suppressed.
[0027] -Acrylic resin (A1)- Examples of acrylic resins (A1) include well-known acrylic polymers. The weight-average molecular weight (Mw) of the acrylic resin (A1) is preferably 5,000 or more and 250,000 or less, more preferably 5,000 or more and 225,000 or less, even more preferably 7,000 or more and less than 200,000, even more preferably 8,000 or more and 100,000 or less, and even more preferably 10,000 or more and 50,000 or less. By having a weight-average molecular weight of the acrylic resin (A1) above the lower limit mentioned above, the dimensional stability (stable over time during storage) of the energy-ray curable resin film (x) can be easily improved, and leakage during standing can be suppressed. Furthermore, by having a weight-average molecular weight of the acrylic resin (A1) below the upper limit mentioned above, the adhesion of the film to the protruding electrode can be improved, and the generation of air bubbles during application can be easily suppressed.
[0028] The glass transition temperature (Tg) of the acrylic resin (A1) is preferably -60 to 70°C, more preferably -40 to 50°C, and even more preferably -30 to 30°C, from the viewpoint of the adhesiveness and handling properties of the energy ray curable resin film (x).
[0029] The acrylic resin (A1) may be a known material, for example, a homopolymer of one acrylic monomer, a copolymer of two or more acrylic monomers, or a copolymer of one or more acrylic monomers and one or more monomers other than acrylic monomers (non-acrylic monomers). The acrylic resin (A1) may be mainly composed of an acrylic monomer. Hereinafter, in this specification, "mainly composed of an acrylic monomer of a polymer" means that the content of the acrylic monomer is 50% by mass or more on a total basis of the polymer, and this content may be 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 97% by mass or more, or 100% by mass.
[0030] Examples of the acrylic monomers constituting the acrylic resin (A1) include acrylic monomers having functional groups that can react with groups of other compounds, and acrylic monomers that do not have such functional groups.
[0031] Examples of functional groups that can react with groups of other compounds include hydroxyl groups, carboxyl groups, amino groups, substituted amino groups (groups in which one or two hydrogen atoms of an amino group are replaced by a group other than a hydrogen atom), and epoxy groups. However, in terms of preventing corrosion of circuits such as semiconductor wafers and semiconductor chips, it is preferable that the functional group is a group other than a carboxyl group. Among these, the functional group is preferably a hydroxyl group.
[0032] The acrylic resin (A1) may be crosslinked with a crosslinking agent in at least a portion of it, or it may not be crosslinked. Examples of acrylic resins that are crosslinked by a crosslinking agent include those in which the functional groups in the acrylic resin react with the crosslinking agent. Specific examples of the functional group are as described above and can be appropriately selected depending on the type of crosslinking agent, and are not particularly limited. For example, when the crosslinking agent is a polyisocyanate compound, the functional group can be a hydroxyl group, a carboxyl group, an amino group, etc., and among these, the hydroxyl group, which has high reactivity with isocyanate groups, is preferred. When the crosslinking agent is an epoxy compound, the functional group can be a carboxyl group, an amino group, etc., and among these, the carboxyl group, which has high reactivity with epoxy groups, is preferred. However, in terms of preventing corrosion of wafer and chip circuits, it is preferable that the functional group is a group other than a carboxyl group.
[0033] Examples of the acrylic monomers constituting the acrylic resin (A1) include (meth)acrylic acid esters such as alkyl (meth)acrylates without functional groups and a cyclic skeleton, (meth)acrylic acid esters without functional groups and having a cyclic skeleton, (meth)acrylic acid esters containing hydroxyl groups, (meth)acrylic acid esters containing carboxyl groups, (meth)acrylic acid esters containing amino groups, (meth)acrylic acid esters containing substituted amino groups, and epoxy group containing (meth)acrylic acid esters; (meth)acrylamide; (meth)acrylamide derivatives, etc.
[0034] In this specification, when a particular compound is assumed to have a structure in which one or more hydrogen atoms are substituted with groups other than hydrogen atoms, a compound having such a substituted structure will be referred to as a "derivative" of the particular compound described above. In this specification, the term "group" includes not only atomic groups formed by the bonding of multiple atoms, but also single atoms.
[0035] Examples of alkyl (meth)acrylate esters that do not have the aforementioned functional group and cyclic skeleton include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, and (meth Examples include alkyl esters such as isononyl acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl ((meth)acrylate) (lauryl (meth)acrylate), tridecyl (meth)acrylate, tetradecyl ((meth)acrylate) (myristyl (meth)acrylate), pentadecyl (meth)acrylate, hexadecyl ((meth)acrylate) (palmityl (meth)acrylate), heptadecyl (meth)acrylate, and octadecyl ((meth)acrylate) (stearyl (meth)acrylate), in which the alkyl group constituting the alkyl ester has a chain structure with 1 to 18 carbon atoms.
[0036] Examples of (meth)acrylic acid esters that do not have the aforementioned functional groups and have a cyclic skeleton include cycloalkyl (meth)acrylic acid esters such as isobornyl (meth)acrylate and dicyclopentanyl (meth)acrylate; (meth)acrylate aryl esters such as phenyl (meth)acrylate and 2-naphthyl (meth)acrylate; (meth)acrylate aralkyl esters such as benzyl (meth)acrylate; (meth)acrylate dicyclopentenyl ester and other cycloalkenyl (meth)acrylates; Examples include cycloalkenyloxyalkyl esters of (meth)acrylate, such as dicyclopentenyloxyethyl (meth)acrylate.
[0037] Examples of the hydroxyl group-containing (meth)acrylic acid ester include (meth)acrylic acid alkyl esters that do not have the functional group and a cyclic skeleton, and (meth)acrylic acid esters that do not have the functional group but have a cyclic skeleton, in which one or more hydrogen atoms are substituted with hydroxyl groups. Specifically, examples include (meth)acrylic acid hydroxyalkyls such as hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; and non-(meth)acrylic unsaturated alcohols such as vinyl alcohol and allyl alcohol (unsaturated alcohols that do not have a (meth)acryloyl skeleton).
[0038] Examples of the carboxyl group-containing (meth)acrylic acid ester include ethylenically unsaturated monocarboxylic acids (monocarboxylic acids having an ethylenically unsaturated bond) such as (meth)acrylic acid and crotonic acid; ethylenically unsaturated dicarboxylic acids (dicarboxylic acids having an ethylenically unsaturated bond) such as fumaric acid, itaconic acid, maleic acid, and citraconic acid; anhydrides of the ethylenically unsaturated dicarboxylic acids; and carboxyalkyl esters of (meth)acrylic acid such as 2-carboxyethyl methacrylate.
[0039] Examples of the substituted amino group-containing (meth)acrylic acid ester include N-methylaminoethyl (meth)acrylic acid.
[0040] Examples of epoxy group-containing monomers include glycidyl group-containing (meth)acrylic acid esters. Specifically, examples include glycidyl (meth)acrylate.
[0041] Examples of the (meth)acrylamide derivatives include N-isopropylacrylamide, N,N-dimethylacrylamide, N-methylacrylamide, N-phenylacrylamide, N-butylacrylamide, and N-(meth)acryloylmorpholine.
[0042] Examples of non-acrylic monomers constituting the acrylic resin (A1) include olefins such as ethylene and norbornene; vinyl acetate; styrene, etc.
[0043] The acrylic resin (A1) preferably contains structural units derived from alkyl (meth)acrylates that do not have functional groups and a cyclic skeleton, hydroxyl group-containing (meth)acrylates, and (meth)acrylamide derivatives. More preferably, the alkyl group constituting the alkyl ester contains structural units derived from alkyl (meth)acrylates that have a chain structure with 1 to 18 carbon atoms, hydroxyl group-containing (meth)acrylates that have a structure in which one hydrogen atom is substituted with a hydroxyl group, and (meth)acrylamide derivatives that have a cyclic structure. It is even more preferable that the acrylic resin (A1) contains structural units derived from methyl acrylate, n-butyl acrylate, N-acryloylmorpholine, and 2-hydroxyethyl acrylate.
[0044] When the acrylic resin (A1) contains acrylic monomers having functional groups (specifically, one or more selected from the group consisting of hydroxyl group-containing (meth)acrylic acid esters, carboxyl group-containing (meth)acrylic acid esters, amino group-containing (meth)acrylic acid esters, substituted amino group-containing (meth)acrylic acid esters, and epoxy group-containing (meth)acrylic acid esters), the ratio (content) of the amount of constituent units derived from the functional group-containing acrylic monomers to the total amount of constituent units constituting the acrylic resin (A1) is preferably 0.1 to 40% by mass, more preferably 1 to 30% by mass, and particularly preferably 5 to 20% by mass. With the ratio within this range, the content of the energy-ray-curable group described later in the acrylic modified resin (A1-1) obtained by the reaction of the acrylic resin (A1) with the energy-ray-curable compound described later can be easily adjusted to a preferred range for the degree of curing of the cured resin film.
[0045] -Acrylic-modified resin (A1-1)- If the acrylic resin (A1) has a functional group, the acrylic resin (A1) may be an acrylic modified resin (A1-1) obtained by the reaction of the functional group with an energy ray curable compound. The energy ray curable compound preferably has one or more groups selected from the group consisting of isocyanate groups, epoxy groups, and carboxyl groups as groups that can react with the functional group of the acrylic resin, and more preferably has an isocyanate group as the group. For example, if the energy ray curable compound has an isocyanate group as the group, this isocyanate group readily reacts with the hydroxyl group of the acrylic resin having a hydroxyl group as the functional group. The energy ray curable group in the energy ray curable compound may be a group containing an energy ray curable double bond, and preferred examples include a (meth)acryloyl group and a vinyl group. An epoxy group may also be used as the energy ray curable group. Furthermore, in the preparation of the acrylic-modified resin (A1-1), as described above, if, for example, the energy-ray-curable compound has an isocyanate group, the isocyanate group reacts with the hydroxyl group of the acrylic resin (A1) to form a urethane bond in the side chain. However, even in this case, if the main chain includes a (meth)acrylic chain and the main component is an acrylic monomer, it shall be classified as an acrylic resin (A1).
[0046] The energy ray curable compound preferably has 1 to 5 energy ray curable groups per molecule, and more preferably 1 to 2.
[0047] Examples of the energy-ray curable compounds include 2-methacryloyloxyethyl isocyanate (MOI), meta-isopropenyl-α,α-dimethylbenzyl isocyanate, methacryloyl isocyanate, allyl isocyanate, and 1,1-(bisacryloyloxymethyl)ethyl isocyanate; Acryloyl monoisocyanate compounds obtained by the reaction of a diisocyanate compound or polyisocyanate compound with hydroxyethyl (meth)acrylate; Examples include acryloyl monoisocyanate compounds obtained by the reaction of a diisocyanate compound or polyisocyanate compound with a polyol compound and hydroxyethyl (meth)acrylate. Among these, the energy ray curable compound is preferably 2-methacryloyloxyethyl isocyanate (MOI).
[0048] The energy-curable compound constituting the acrylic-based modified resin (A1-1) may consist of only one type or two or more types, and if there are two or more types, their combination and ratio can be arbitrarily selected.
[0049] In the acrylic resin, the ratio of the content of energy-ray-curable groups derived from the energy-ray-curable compound to the content of the functional groups derived from the acrylic resin is preferably 20 to 120 mol%, more preferably 35 to 100 mol%, and particularly preferably 50 to 100 mol%. Having the content within this range increases the adhesive strength of the protective film after curing. Note that if the energy-ray-curable compound is a monofunctional compound (having one of the groups in one molecule), the upper limit of the content is 100 mol%, but if the energy-ray-curable compound is a polyfunctional compound (having two or more of the groups in one molecule), the upper limit of the content may exceed 100 mol%.
[0050] In an energy-ray curable resin film (x) and an energy-ray curable resin composition (x1), the polymer component (A) may consist only of an acrylic resin (A1). Furthermore, if the polymer component (A) contains components other than the acrylic resin (A1), the content of the acrylic resin (A1) is preferably 30 to 80% by mass, more preferably 40 to 70% by mass, and even more preferably 50 to 60% by mass, based on the total amount of the polymer component (A). Based on the above, the acrylic resin (A1) may be 30-100% by mass, 40-100% by mass, or 50-100% by mass, based on the total amount of polymer component (A).
[0051] In this embodiment, the energy-ray curable resin film (x) and energy-ray curable resin composition (x1) preferably contain a small amount of acrylic resin that does not fall under the category of acrylic resin (A1) (hereinafter referred to as acrylic resin (A1)'), from the viewpoint of easily suppressing seepage during standing and the generation of air bubbles during application. The content of acrylic resin (A1)' is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 1 part by mass or less, and even more preferably not contained, per 100 parts by mass of acrylic resin (A1).
[0052] -Urethane resin (A2)- The urethane resin (A2) is not particularly limited as long as it is a polymer having one or more urethane bonds and urea bonds in its main chain, and known polymers can be used, for example, urethane (meth)acrylate resins.
[0053] The urethane (meth)acrylate resin is not particularly limited as long as it has (meth)acryloyl groups and urethane bonds. For example, it can be obtained by esterifying a polyurethane prepolymer, which is obtained by reacting a compound such as a polyalkylene polyol, polyether polyol, polyester polyol, polycarbonate polyol, hydrogenated isoprene with hydroxyl group terminus, or hydrogenated butadiene with hydroxyl group terminus) with a polyisocyanate, with (meth)acrylic acid or a (meth)acrylic acid derivative. However, even if a urethane (meth)acrylate resin contains (meth)acryloyl groups in its molecule, it has urethane bonds in its main chain and its main component is not an acrylic monomer, and is classified as a urethane resin (A2).
[0054] Examples of polyalkylene polyols used in the production of urethane (meth)acrylate resins include polypropylene glycol, polyethylene glycol, polybutylene glycol, and polyhexylene glycol. If the resulting urethane (meth)acrylate resin has three or more functional groups, appropriate combinations of glycerin, trimethylolpropane, triethanolamine, pentaerythritol, ethylenediamine, diethylenetriamine, sorbitol, sucrose, etc., may be used.
[0055] Examples of polyisocyanates used in the production of urethane (meth)acrylate resins include aliphatic diisocyanates such as hexamethylene diisocyanate and trimethylene diisocyanate; aromatic diisocyanates such as tolylene diisocyanate, xylylene diisocyanate, and diphenyl diisocyanate; and alicyclic diisocyanates such as dicyclohexylmethane diisocyanate and isophorone diisocyanate. Polyisocyanates are not limited to bifunctional polyisocyanates; trifunctional polyisocyanates or those with three or more functionalities can also be used.
[0056] Examples of (meth)acrylic acid derivatives used in the production of urethane (meth)acrylate resins include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate; 2-isocyanate ethyl acrylate, 2-isocyanate ethyl methacrylate, and 1,1-bis(acryloxymethyl)ethyl isocyanate.
[0057] Another method for producing urethane (meth)acrylate resins involves reacting the hydroxyl groups of compounds such as polyalkylene polyols, polyether polyols, polyester polyols, polycarbonate polyols, hydrogenated isoprene with hydroxyl group termini, and hydrogenated butadiene with hydroxyl group termini with the -N=C=O moiety of isocyanate alkyl (meth)acrylate. In this case, examples of isocyanate alkyl (meth)acrylates that can be used include the above-mentioned 2-isocyanate ethyl acrylate, 2-isocyanate ethyl methacrylate, and 1,1-bis(acryloxymethyl)ethyl isocyanate.
[0058] The weight-average molecular weight (Mw) of the urethane resin (A2) is preferably 5,000 or more and less than 100,000, more preferably 5,000 or more and 50,000 or less, even more preferably 6,000 or more and less than 25,000, even more preferably 7,000 or more and 20,000 or less, and even more preferably 7,000 or more and 15,000 or less. Having a weight-average molecular weight of urethane resin (A2) above the lower limit above makes it easier to improve the dimensional stability (stable over time during storage) of the energy-ray curable resin film (x). Also, having a weight-average molecular weight of urethane resin (A2) below the upper limit above makes it possible to lower the storage modulus (E'1) of the energy-ray curable resin film (x) at 40°C before curing.
[0059] The glass transition temperature (Tg) of the urethane resin (A2) is preferably -60 to 70°C, more preferably -40 to 50°C, and even more preferably -30 to 30°C, from the viewpoint of the adhesiveness and handling properties of the energy ray curable resin film.
[0060] In an energy-ray curable resin film (x) and an energy-ray curable resin composition (x1), if the polymer component (A) contains a urethane resin (A2), the content of the urethane resin (A2) is preferably 10 to 70% by mass, more preferably 30 to 60% by mass, and even more preferably 40 to 50% by mass, based on the total amount of polymer component (A).
[0061] In the energy-ray curable resin film (x) and the energy-ray curable resin composition (x1), the content of polymer component (A) is preferably 10 to 70% by mass, more preferably 15 to 65% by mass, and even more preferably 20 to 60% by mass, based on the total amount of active ingredients.
[0062] Examples of polyarylate resins in polymer component (A) include known resins, such as those whose basic structure is the polycondensation of a divalent phenol with a dibasic acid such as phthalic acid or a carboxylic acid. Among these, polycondensates of bisphenol A and phthalic acid, poly-4,4'-isopropylidenediphenylene terephthalate / isophthalate copolymers, and their derivatives are preferred.
[0063] Examples of the acetal resin in polymer component (A) include those that are well known. Among these, preferred acetal resins include, for example, polyvinyl formal and polyvinyl butyral, with polyvinyl butyral being the most preferred. Examples of polyvinyl butyral include those having constituent units represented by the following formulas (i)-1, (i)-2, and (i)-3.
[0064] [ka]
[0065] (In the formula, l, m, and n are each an independent integer greater than or equal to 1.)
[0066] The weight-average molecular weight (Mw) of the polyvinyl acetal resin (preferably polyvinyl butyral) is preferably 5,000 to 200,000, and more preferably 8,000 to 100,000. Having a weight-average molecular weight of the polyvinyl acetal resin (preferably polyvinyl butyral) above the lower limit makes it easier to improve the shape stability (stable over time during storage) of the energy-ray curable resin film (x). Furthermore, having a weight-average molecular weight of the polyvinyl acetal resin (preferably polyvinyl butyral) below the upper limit makes it easier for the energy-ray curable resin film (x) to conform to the uneven surface of the adherend, for example, making it easier to suppress the generation of voids between the adherend and the energy-ray curable resin film (x). Therefore, the coverage of the surface where protruding electrodes are formed is improved, and the ability to embed into irregularities that the component may have is also improved.
[0067] The glass transition temperature (Tg) of the polyvinyl acetal resin (preferably polyvinyl butyral) is preferably 40 to 80°C, and more preferably 50 to 70°C, from the viewpoint of the film-forming properties of the energy-ray curable resin film (x) and the protrusion of the tops of the protruding electrodes on the protruding electrode forming surface. Herein, in this specification, "the ability of the top of the protruding electrode to penetrate the energy ray-curable resin film (x) when the energy ray-curable resin film (x) is attached to the surface on which the protruding electrode is formed" refers to the ability of the top of the protruding electrode to penetrate the energy ray-curable resin film (x), and is also referred to as "the ability of the top of the protruding electrode to penetrate".
[0068] The ratio of three or more monomers that make up the polyvinyl acetal resin (preferably polyvinyl butyral) can be arbitrarily selected.
[0069] (Compound component (B)) The energy-ray curable resin film (x) and the energy-ray curable resin composition (x1) contain compound component (B). As stated above, in this application, compound component (B) refers to a compound having an energy-ray curable group and a weight-average molecular weight of less than 5,000. Compound component (B) is a component for curing the energy-ray curable resin film (x) to form a hard cured resin film. Furthermore, the curing (polymerization) reactions that compound component (B) can induce include polycondensation reactions. Compound component (B) may be used alone or in combination of two or more types. If compound component (B) consists of two or more types, their combination and ratio can be arbitrarily selected. The energy-ray curable groups of compound component (B) mainly include radical polymerizable functional groups, cationic polymerizable functional groups, and anionic polymerizable functional groups. The radical polymerizable functional group is not particularly limited, but examples include groups containing energy-ray curable double bonds, specifically (meth)acryloyl groups, vinyl groups, and the like. The cationic polymerizable functional group is not particularly limited, but examples include alicyclic ether groups (epoxy groups, oxetanyl groups, etc.) and vinyl ether groups. The anionic polymerizable functional group is not particularly limited, but examples include alicyclic ether groups (epoxy groups, oxetanyl groups, etc.), cyclic sulfide groups, styrene groups, and acrylonitrile groups. In this specification, a radical polymerizable functional group is also considered to belong to the category of radical polymerizable functional groups if it possesses at least one of the properties of cationic polymerizability and anionic polymerizability. In other words, specific examples of compound component (B) include radical polymerizable energy ray curable compounds (B1), cationic polymerizable energy ray curable compounds (B2), and anionic polymerizable energy ray curable compounds (B3). In this specification, a radical polymerizable energy ray curable compound (B1) is also considered to belong to the category of radical polymerizable energy ray curable compound (B1) if it possesses at least one of a cationic polymerizable functional group and an anionic polymerizable functional group. Among these, the energy-ray curable resin film (x) of this embodiment contains a radical polymerizable energy-ray curable compound (B1) with a weight-average molecular weight of less than 5,000 as the compound component (B). Hereafter, radical polymerizable energy ray curable compounds (B1) with a weight-average molecular weight of less than 5,000 will also be simply referred to as radical polymerizable energy ray curable compounds (B1).
[0070] The weight-average molecular weight of compound component (B) is not particularly limited, but from the viewpoint of the curability of the energy-ray-curable resin film (x) and the strength and heat resistance of the cured resin film after curing, it is preferably 100 or more and less than 5,000, more preferably 200 or more and 3,500 or less, and even more preferably 300 or more and 2,500 or less.
[0071] The number-average molecular weight of compound component (B) is not particularly limited, but from the viewpoint of the curability of the energy-ray-curable resin film (x) and the strength and heat resistance of the cured resin film after curing, it is preferably 100 or more and less than 5,000, more preferably 150 or more and 3,000 or less, and even more preferably 200 or more and 2,000 or less. Furthermore, if compound component (B) contains multiple components, the weight-average molecular weight and number-average molecular weight of each component contained in compound component (B) shall satisfy the above range.
[0072] (Radical polymerizable energy ray curable compound (B1)) The radical polymerizable energy ray curable compound (B1) is not particularly limited as long as it satisfies the above conditions, but examples include low molecular weight compounds having energy ray curable double bonds, epoxy resins having energy ray curable double bonds, and phenolic resins having energy ray curable double bonds.
[0073] Examples of the radical polymerizable energy ray curable compound (B1) include polyfunctional monomers or polymers, and acrylate compounds having a (meth)acryloyl group are preferred. Examples of the acrylate compounds include 2-hydroxy-3-(meth)acryloyloxypropyl methacrylate, polyalkylene glycol (meth)acrylates such as polyethylene glycol di(meth)acrylate, propoxylated ethoxylated bisphenol E di(meth)acrylate, 2,2-bis[4-((meth)acryloxypolyethoxy)phenyl]propane, ethoxylated bisphenol A di(meth)acrylate, 2,2-bis[4-((meth)acryloxydiethoxy)phenyl]propane, 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene, 2,2-bis[4-((meth)acryloxypolypropoxy)phenyl]propane, tricyclodecanedimethanol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, and 1,4-butylene glycoside. Difunctional (meth)acrylates such as di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, 2,2-bis[4-(meth)acryloxyethoxy)phenyl]propane, neopentyl glycol di(meth)acrylate, ethoxylated polypropylene glycol di(meth)acrylate, 2-hydroxy-1,3-di(meth)acryloxypropane, and dicyclopentanyl di(meth)acrylate; Tris(2-(meth)acryloxyethyl) isocyanurate, ε-caprolactone modified tris-(2-(meth)acryloxyethyl) isocyanurate, ethoxylated glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, ethoxylated pentaerythritol tetra( Polyfunctional (meth)acrylates such as meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol poly(meth)acrylate, and dipentaerythritol hexa(meth)acrylate; Oligoester (meth)acrylate; epoxy-modified (meth)acrylate; polyether (meth)acrylate other than the above polyalkylene glycol (meth)acrylate; Examples include polyfunctional (meth)acrylate polymers such as urethane (meth)acrylate polymers; and itaconic acid polymers. Among these acrylate compounds, it is preferable that one or more are selected from polyfunctional (meth)acrylates and polyfunctional (meth)acrylate polymers, more preferably that one or more are selected from ε-caprolactone-modified tris-(2-(meth)acryloxyethyl)isocyanurate and urethane (meth)acrylate polymers, and even more preferably that ε-caprolactone-modified tris-(2-(meth)acryloxyethyl)isocyanurate is the most preferable.
[0074] Among the radical polymerizable energy ray curable compounds (B1), epoxy resins having energy ray curable groups, and acrylate-based compounds and phenolic resins having energy ray curable groups that also have epoxy groups, may also be resins that constitute cationic polymerizable energy ray curable compounds (B2) or anionic polymerizable energy ray curable compounds (B3) described later, but in the present invention, they are treated as radical polymerizable energy ray curable compounds (B1).
[0075] In the energy ray curable resin film (x) and the energy ray curable resin composition (x1), the content of the radical polymerizable energy ray curable compound (B1) is preferably 80 to 100% by mass, more preferably 90 to 100% by mass, and even more preferably 100% by mass, based on the total amount of compound component (B).
[0076] In the energy-ray curable resin film (x) and the energy-ray curable resin composition (x1), the content of the acrylate compound is preferably 80 to 100% by mass, more preferably 90 to 100% by mass, and even more preferably 100% by mass, based on the total amount of compound component (B).
[0077] In the energy ray curable resin film (x) and the energy ray curable resin composition (x1), the content of the radical polymerizable energy ray curable compound (B1) is preferably 5 to 1,000 parts by mass, more preferably 10 to 500 parts by mass, and even more preferably 15 to 250 parts by mass, per 100 parts by mass of the polymer component (A), from the viewpoint of enhancing the protective properties of the cured resin film.
[0078] (Cationically polymerizable energy ray curable compound (B2)) The cationic polymerizable energy ray curable compound (B2) is not particularly limited as long as it satisfies the above conditions, but for example, it can be used in combination with an epoxy resin that is solid at room temperature (hereinafter also referred to as a solid epoxy resin) and an epoxy resin that is liquid at room temperature (hereinafter also referred to as a liquid epoxy resin). In this specification, "room temperature" refers to 5 to 35°C, preferably 15 to 25°C.
[0079] The liquid epoxy resin is not particularly limited as long as it is liquid at room temperature. Examples include bisphenol A type epoxy resin, bisphenol F type epoxy resin, novolac type epoxy resin, glycidyl ester type epoxy resin, biphenyl type epoxy resin, and phenylene skeleton type epoxy resin. Among these, bisphenol A type epoxy resin may also be used. Liquid epoxy resin may be used alone or in combination of two or more types. When two or more types of liquid epoxy resin are used, their combination and ratio can be arbitrarily selected.
[0080] The epoxy equivalent of the liquid epoxy resin may preferably be 200 to 600 g / eq, more preferably 250 to 550 g / eq, and even more preferably 300 to 500 g / eq. The epoxy equivalent in this embodiment can be measured in accordance with JIS K 7236:2009.
[0081] The solid epoxy resin is not particularly limited as long as it is solid at room temperature. Examples include biphenyl-type epoxy resin, bisphenol A-type epoxy resin, bisphenol F-type epoxy resin, orthocresol novolac epoxy resin, dicyclopentadiene-type epoxy resin, naphthalene-type epoxy resin, anthracene-type epoxy resin, and fluorene-based epoxy resin. Among these, naphthalene-type epoxy resin, dicyclopentadiene-type epoxy resin, and fluorene-based epoxy resin are preferred, and dicyclopentadiene-type epoxy resin may also be used. Solid epoxy resins may be used individually or in combination of two or more types. If two or more types of solid epoxy resins are used, their combination and ratio can be arbitrarily selected.
[0082] The epoxy equivalent of the solid epoxy resin may be 150-450 g / eq or 150-400 g / eq.
[0083] The ratio of liquid epoxy resin (xe) to solid epoxy resin (ye) [(xe) / (ye)] may be 0.01 to 10.0, 0.02 to 8.0, or 0.03 to 6.0 by mass. When the above ratio [(xe) / (ye)] is within the above range, it is possible to suppress the generation of cutting chips and the like when cutting the cured resin film with a dicing blade after curing, thereby improving machinability.
[0084] (Anionic polymerizable energy ray curable compound (B3)) The anionic polymerizable energy ray curable compound (B3) is not particularly limited as long as it satisfies the above conditions, but examples include epoxy resins and cyclic ether compounds such as oxetane compounds, cyclic ester compounds such as lactone compounds, and cyclic sulfide compounds such as episulfide compounds, as mentioned above in the section on cationic polymerizable energy ray curable compounds (B2).
[0085] In the energy-ray curable resin film (x) and the energy-ray curable resin composition (x1), the content of compound component (B) is preferably 5 to 1,000 parts by mass, more preferably 10 to 500 parts by mass, and even more preferably 15 to 250 parts by mass, based on 100 parts by mass of polymer component (A), from the viewpoint of enhancing the protective properties of the cured resin film.
[0086] (Photopolymerization initiator (C)) The energy-ray curable resin film (x1) and the energy-ray curable resin composition (x1-1) preferably contain a photopolymerization initiator (C) in order to efficiently advance the radical polymerization reaction of the energy-ray curable resin.
[0087] The photopolymerization initiator (C) is not particularly limited as long as it generates radicals when energy is applied by irradiation with active energy rays such as ultraviolet light, radiation, or electron beams, but for example, benzoin compounds such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, benzoin benzoic acid, benzoin methyl benzoate, and benzoin dimethyl ketal; acetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 2,2-dimethoxy-1,2-diphenylethane-1-one, 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropan-1-one, 2-(dimethylamino)-1-(4-morpholinophenyl)-2-benzyl-1-butanone, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4- Examples include acetophenone compounds such as morpholinyl)phenyl]-1-butanone; acylphosphine oxide compounds such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide; sulfide compounds such as benzylphenyl sulfide and tetramethylthiuram monosulfide; α-ketol compounds such as 1-hydroxycyclohexylphenyl ketone; azo compounds such as azobisisobutyronitrile; titanocene compounds such as titanocene; thioxanthone compounds such as thioxanthone; peroxide compounds; diketone compounds such as diacetyl; benzyl; dibenzyl; benzophenone; 2,4-diethylthioxanthone; 1,2-diphenylmethane; 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone; and quinone compounds such as 1-chloroanthraquinone and 2-chloroanthraquinone. Furthermore, examples of photopolymerization initiators include photosensitizers such as amines. Among these, acetophenone compounds are preferred, and 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone is more preferred.
[0088] The photopolymerization initiator (C) contained in the energy-ray curable resin film (x) and the energy-ray curable resin composition (x1) may be only one type or two or more types, and if there are two or more types, their combination and ratio can be arbitrarily selected. For example, a highly reactive photopolymerization initiator that is liquid at room temperature, such as 2-hydroxy-2-methyl-1-phenylpropan-1-one, can be used alone to efficiently crosslink the energy-ray curable resin film (x). A less reactive photopolymerization initiator, such as 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropan-1-one or 1-hydroxycyclohexyl-phenyl ketone, can be used in combination with a highly reactive photopolymerization initiator such as 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone to efficiently crosslink the energy-ray curable resin film (x).
[0089] In the energy-ray curable resin film (x) and the energy-ray curable resin composition (x1), the content of the photopolymerization initiator (C) is preferably 0.1 to 20 parts by mass, more preferably 1 to 10 parts by mass, and even more preferably 1 to 5 parts by mass, based on 100 parts by mass of the content of the radical-polymerizable energy-ray curable compound (B1). When the content of the photopolymerization initiator (C) is above the lower limit, the curing of the energy-ray curable resin film (x1) proceeds more easily. Furthermore, when the content of the photopolymerization initiator (C) is below the upper limit, the amount of unreacted photopolymerization initiator (C) remaining in the cured resin film can be reduced.
[0090] (Photoacid generator (D1)) The energy ray-curable resin film (x) and the energy ray-curable resin composition (x1) of the present embodiment may or may not contain the photoacid generator (D1).
[0091] The photoacid generator (D1) is not particularly limited as long as it generates an acid when energy is applied by irradiation with active energy rays such as ultraviolet rays, radiation, and electron beams, and examples thereof include onium salts such as sulfonium salts, iodonium salts, diazonium salts, selenium salts, pyridinium salts, ferrocenium salts, phosphonium salts, thiopyrinium salts, selenium salts, oxonium salts, ammonium salts, and bromine salts, and is preferably one or more selected from aromatic sulfonium salts and aromatic iodonium salts. Aromatic sulfonium salts and aromatic iodonium salts are commercially available, and commercial products may be used. Further, examples of the anion component include [(Ar) n1 B(Phf) 4-n1 - (wherein Ar represents a phenyl group or a biphenylyl group; B represents boron; Phf represents a phenyl group in which one or more hydrogen atoms are substituted with one or more selected from a perfluoroalkyl group, a perfluoroalkoxy group, and a halogen atom; n1 represents an integer of 0 to 3), BF4 - , [(Rf) m2 PF 6-m2 - (Rf represents an alkyl group in which 80% or more of hydrogen atoms are substituted with fluorine atoms; P represents phosphorus; F represents fluorine; m2 represents an integer of 0 to 5), BF4 - , PF6 - , AsF6 - , SbF6 - , SbF5OH - , and B(C6F5) 4- and the like.
[0092] Examples of photocationic polymerization initiators include diphenyl[4-(phenylthio)phenyl]sulfonium hexafluorophosphate, (4-hydroxyphenyl)methylbenzylsulfonium tetrakis(pentafluorophenyl)borate, 4-(4-biphenylylthio)phenyl-4-biphenylylphenylsulfonium tetrakis(pentafluorophenyl)borate, 4-(phenylthio)phenyldiphenylsulfonium phenyltris(pentafluorophenyl)borate, [4-(4-biphenylylthio)phenyl]-4-biphenylylphenylsulfonium phenyltris(pentafluorophenyl)borate, diphenyl[4-(phenylthio)phenylsulfonium] hexafluoroantimonate, diphenyl[4-(phenylthio)phenyl]sulfonium tris(pentafluoroethyl)trifluorophosphate, diphenyl[4-(phenylthio)phenyl]sulfonium tetrakis(pentafluorophenyl)borate, and 4-(4-biphenylylthio)phenyl-4-biphenylylphenylsulfonium Examples include tris(pentafluoroethyl)trifluorophosphate, bis[4-(diphenylsulfonio)phenyl]sulfide phenyltris(pentafluorophenyl)borate, and [4-(2-thiooxantonylthio)phenyl]phenyl-2-thiooxantonylsulfonium phenyltris(pentafluorophenyl)borate. These may be used individually or in combination of two or more types.
[0093] In the energy-ray curable resin film (x) and the energy-ray curable resin composition (x1), when a photoacid generator (D1) is used, the content of the photoacid generator (D1) may be 0.1 to 20 parts by mass, 1 to 10 parts by mass, or 3 to 10 parts by mass, per 100 parts by mass of the content of the cationic polymerizable energy-ray curable compound (B2). When the content of the photoacid generator (D1) is above the lower limit, the curing of the energy-ray curable resin film (x1) proceeds more easily. Furthermore, when the content of the photoacid generator (D1) is below the upper limit, the amount of unreacted photoacid generator (D1) remaining in the cured resin film can be reduced.
[0094] (Photobase Generator (D2)) The energy-ray curable resin film (x) and energy-ray curable resin composition (x1) of this embodiment may or may not contain a photobase generator (D2).
[0095] Of these, the photobase generator (D2) is not particularly limited as long as it generates a base when energy is applied by irradiation with active energy rays such as ultraviolet rays, radiation, or electron beams, but examples include α-aminoacetophenone compounds; oxime ester compounds; compounds having substituents such as acyloxyimino groups, N-formylated aromatic amino groups, N-acylated aromatic amino groups, nitrobenzylcarbamate groups, and alkoxybenzylcarbamate groups. Furthermore, the photobase generator (D2) may be a commercially available product such as 9-anthramethyl N,N'-diethylcarbamate, (E)-1-[3-(2-hydroxyphenyl)-2-propenoyl]piperidine, guanidium 2-(3-benzoylphenyl)propionate, 1-(anthraquinone-2-yl)ethylimidazole carboxylate, 1,2-diisopropyl-3-[bis(dimethylamino)methylene]guanidium 2-(3-benzoylphenyl)propionate, or 1,2-dicyclohexyl-4,4,5,5-tetramethylbiguanidium n-butyltriphenyl borate. The above photobase generators (D2) may be used individually or in combination of two or more types.
[0096] In the energy-ray curable resin film (x) and the energy-ray curable resin composition (x1), when a photobase generator (D2) is used, the content of the photobase generator (D2) may be 0.1 to 20 parts by mass, 1 to 10 parts by mass, or 3 to 10 parts by mass per 100 parts by mass of the anionic polymerizable energy-ray curable compound (B3). When the content of the photobase generator (D2) is above the lower limit, the curing of the energy-ray curable resin film (x1) proceeds more easily. Furthermore, when the content of the photobase generator (D2) is below the upper limit, the amount of unreacted photobase generator (D2) remaining in the cured resin film can be reduced.
[0097] (Filling material (E)) The energy-ray curable resin film (x) and the energy-ray curable resin composition (x1) may contain a filler (E). By including a filler (E) and satisfying the above parameters, the chipping suppression of the cured resin film obtained by curing the energy ray curable resin film (x) can be easily improved. Furthermore, the inclusion of filler (E) makes it easier to adjust the thermal expansion coefficient of the cured resin film obtained by curing the energy-ray curable resin film (x) to an appropriate range, thereby further improving the reliability of the package obtained using the energy-ray curable resin film (x). In addition, the inclusion of filler (E) in the energy-ray curable resin film (x) can reduce the moisture absorption rate of the cured resin film and improve its heat dissipation.
[0098] The filler (E) may be either an organic filler or an inorganic filler, but it is preferably an inorganic filler or an organic / inorganic hybrid filler. Preferred inorganic fillers include, for example, powders such as silica, talc, calcium carbonate, and boron nitride; beads formed from these inorganic fillers in a spherical shape; surface-modified products of these inorganic fillers; single-crystal fibers of these inorganic fillers; and glass fibers. Preferred organic / inorganic hybrid fillers include, for example, component-mixed fillers such as silica-acrylic composite particles (e.g., Soliostar manufactured by Nippon Shokubai); and composite fillers incorporating inorganic fine particles with organic materials. Among these, inorganic fillers are preferred, and among inorganic fillers, silica is preferred.
[0099] The filler (E) may be used alone or in combination of two or more types. If there are two or more types of fillers (E), their combinations and ratios can be selected arbitrarily.
[0100] In energy-ray curable resin films (x) and energy-ray curable resin compositions (x1), when a filler (E) is used, the content of the filler (E) is preferably 5 to 50% by mass, more preferably 7 to 40% by mass, and even more preferably 15 to 35% by mass, based on the total amount of active ingredients, from the viewpoint of suppressing peeling of the cured resin film from the chip due to thermal expansion and contraction.
[0101] The average particle size of the filler (E) is preferably 500 nm or less, more preferably 5 to 300 nm, and particularly preferably 10 to 100 nm. In this specification, the particle size of the filler (E) refers to the arithmetic mean particle size obtained by randomly selecting and measuring the particle sizes of multiple primary particles of the filler (E) observed with an electron microscope, and calculating the average value of these measurements.
[0102] (Additive (F)) The energy-ray curable resin film (x) and the energy-ray curable resin composition (x1) may contain an additive (F) within a range that does not impair the effects of the present invention. The additive (F) may be any known additive and can be arbitrarily selected depending on the purpose, and is not particularly limited. Preferred additives (F) include, for example, colorants, UV absorbers, photosensitizers, hindered amine stabilizers, rheology control agents, coupling agents, crosslinking agents, surfactants, plasticizers, antistatic agents, antioxidants, leveling agents, gettering agents, and silicone oils.
[0103] Additive (F) may be used alone or in combination of two or more types. If there are two or more types of additive (F), their combination and ratio can be arbitrarily selected. The amount of additive (F) is not particularly limited and should be selected as appropriate depending on the purpose.
[0104] (solvent) The energy-ray curable resin composition (x1) preferably further contains a solvent. The energy-ray curable resin composition (x1) containing a solvent has good handling properties. The solvent is not particularly limited, but preferred solvents include, for example, hydrocarbons such as toluene and xylene; alcohols such as methanol, ethanol, 2-propanol, isobutyl alcohol (2-methylpropan-1-ol), and 1-butanol; esters such as ethyl acetate; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran; and amides (compounds having an amide bond) such as dimethylformamide and N-methylpyrrolidone. The solvent may be used alone or in combination of two or more types. If two or more solvents are used, their combination and ratio can be arbitrarily selected. The solvent is preferably methyl ethyl ketone or the like, as it allows for more uniform mixing of the components contained in the energy-curable resin composition (x1).
[0105] -Method for preparing an energy ray-curable resin composition (x1)- An energy-ray curable resin composition (x1) is obtained by blending the components that constitute it. The order in which the components are added during blending is not particularly limited, and two or more components may be added simultaneously. When using a solvent, the solvent may be used after pre-diluting the mixture by mixing it with any of the other components, or the solvent may be used by mixing it with the other components without pre-diluting them. The method of mixing each component during formulation is not particularly limited, and any known method may be appropriately selected, such as mixing by rotating a stirring bar or impeller; mixing using a mixer; or mixing by applying ultrasound. The temperature and time during the addition and mixing of each component are not particularly limited as long as the components do not deteriorate, and can be adjusted as appropriate, but a temperature of 15 to 30°C is preferred.
[0106] <Storage modulus (E'1) at 40°C before hardening> In the energy-ray curable resin film of this embodiment, from the viewpoint of improving the adhesion of the film to the protruding electrode and making it easier to suppress the generation of air bubbles during application, it is preferable that the storage modulus (E'1) at 40°C before curing is 20 MPa or less. Here, from the viewpoint of making it easier to suppress the generation of air bubbles, the storage modulus (E'1) of the energy ray curable resin film at 40°C before curing is preferably 17 MPa or less, more preferably 15 MPa or less, even more preferably 10 MPa or less, even more preferably 8 MPa or less, and still more preferably 5 MPa or less. Furthermore, the storage modulus (E'1) of the energy-ray curable resin film at 40°C before curing is preferably 1 MPa or higher, more preferably 1.6 MPa or higher, and even more preferably 2 MPa or higher, from the viewpoint of suppressing seepage during standing. The storage modulus (E'1) of an energy-ray curable resin film at 40°C before curing can be measured by the method described in the examples below. Furthermore, the storage modulus (E'1) of the energy-ray curable resin film at 40°C before curing can be adjusted by adjusting either or both of the types and content of components contained in the composition for forming the energy-ray curable resin film.
[0107] <Storage modulus (E'2) at 25°C after curing> In the energy-ray curable resin film of this embodiment, the storage modulus (E'2) at 25°C after curing is preferably 10,000 MPa or less, more preferably 8,500 MPa or less, even more preferably 7,000 MPa or less, even more preferably 6,000 MPa or less, and still more preferably 5,000 MPa or less, from the viewpoint of ensuring the flexibility of the cured resin film. Furthermore, the storage modulus (E'2) of the energy-ray curable resin film at 25°C after curing is preferably 500 MPa or higher, more preferably 1,000 MPa or higher, even more preferably 1,200 MPa or higher, even more preferably 1,500 MPa or higher, and still more preferably 1,800 MPa or higher, from the viewpoint of improving the protective properties of the protruding electrode formation surface. Furthermore, the storage modulus (E'2) of the energy-ray curable resin film at 25°C after curing can be adjusted by adjusting either or both of the types and / or amounts of components contained in the composition for forming the energy-ray curable resin film. The storage modulus (E'2) of an energy-ray curable resin film at 25°C after curing can be measured, for example, by the following method. First, multiple energy-ray curable resin films with a thickness of 30 μm are prepared. Next, while removing the release films from these films, the exposed surfaces of the energy-ray curable resin films are bonded together to create a laminate of multiple protective film-forming films (60 μm thick). Next, the laminate is treated with an irradiation device (Lintec RAD2000m / 8) on both sides, at an irradiation intensity of 200 mW / cm². 2 , cumulative light intensity 300 mJ / cm 2Under these conditions, the energy-ray-curable resin film is cured by irradiating it with ultraviolet light twice to form a cured resin film. After obtaining a laminate of multiple cured resin films in this manner, a test specimen (cured resin film test specimen, thickness 60 μm, length 30 mm in the tensile direction in the tensile mode described later) is prepared by making its width 5 mm. Next, using a dynamic mechanical analyzer (DMA Q800 manufactured by T.A. Instruments), the storage modulus E' from 0°C to 300°C was measured under the following measurement conditions: tensile method (tensile mode), chuck distance: 20 mm, frequency: 11 Hz, heating rate: 3°C / min, amplitude: 5 μm, and constant-rate heating.
[0108] <Ratio of the storage modulus at 40°C before curing (E'1) to the storage modulus at 25°C after curing (E'2) [(E'1) / (E'2)]> In the energy-ray curable resin film of this embodiment, the ratio [(E'1) / (E'2)] of the storage modulus at 40°C before curing (E'1) to the storage modulus at 25°C after curing (E'2) is preferably 0.00010 to 0.0060, more preferably 0.00030 to 0.0050, and even more preferably 0.00060 to 0.0045, from the viewpoint of maintaining a balance between suppressing air bubbles during application and the strength of the cured resin film.
[0109] The thickness of the energy-ray curable resin film is adjusted as appropriate, taking into consideration the thickness of the cured resin film formed by curing the energy-ray curable resin film, the unevenness of the circuit-forming surface of the component (for example, the height and number of protruding electrodes (installation density of protruding electrodes)), etc. The thickness of the energy-ray curable resin film is preferably 5 to 70 μm, more preferably 10 to 60 μm, and even more preferably 15 to 45 μm. If the thickness of the energy-ray-curable resin film is greater than or equal to the lower limit mentioned above, it is easier to produce a film with high in-plane uniformity, and insulation is ensured because it can follow the circuit formation surface without any gaps. On the other hand, if the thickness of the energy-ray-curable resin film is less than or equal to the upper limit mentioned above, it is possible to prevent the energy-ray-curable resin film from becoming excessively thick, making it possible to create thinner semiconductor devices.
[0110] Here, the thickness T [μm] of the energy-curable resin film may be calculated using the following formula. T = H × (100 - Vb) / 100 In the above formula, H is the height of the protruding electrode [μm], and Vb is the percentage [%] of the space occupied by the protruding electrode in the space between the surface where the curved protruding electrode is formed and the surface formed by connecting the vertices of the protruding electrode on the protruding electrode forming surface of the member. The thickness T [μm] of the energy-curable resin film calculated using the above formula may vary by approximately 10%.
[0111] (Preparation of energy ray curable resin film (x)) The energy-ray curable resin film (x) can be manufactured, for example, by coating the surface to be formed with the energy-ray curable resin composition (x1) of this embodiment and drying it as necessary. The energy ray curable resin composition (x1) can be applied by known methods, such as using various coaters including an air knife coater, blade coater, bar coater, gravure coater, roll coater, roll knife coater, curtain coater, die coater, knife coater, screen coater, Meyer bar coater, and kiss coater. The drying conditions after applying the energy-ray curable resin composition (x1) are not particularly limited, but for example, the drying temperature can be set to 70 to 130°C and the drying time to 10 seconds to 5 minutes.
[0112] <Structure of a composite sheet> The energy-curable resin film (x) of this embodiment may be a single-layer film or may be formed on the release surface of a release film, but from the viewpoint of improving handling and other aspects, it is preferable to be a composite sheet with a support sheet. The following describes the configuration examples of the composite sheet of this embodiment, specifically the first to third embodiments. However, the configuration examples of the composite sheet of this embodiment are not limited to the first to third embodiments. For example, the first to third embodiments may of course have other layers, as long as they do not significantly impair the effects of the present invention.
[0113] (First aspect) Figure 1 shows a first embodiment of the composite sheet of this embodiment. The composite sheet 1a shown in Figure 1 comprises a base material 10 and an energy-ray curable resin film (x). In the first embodiment, the support sheet is the base material 10. Although not shown, a release film or the like may be provided on the side of the energy-ray curable resin film (x) opposite to the base material 10.
[0114] (Second aspect) A second embodiment of the composite sheet of this embodiment is shown in Figure 2. The composite sheet 1b shown in Figure 2 comprises a base material 10, a buffer layer 11, and an energy-ray curable resin film (x) in that order. In the second embodiment, the support sheet is a laminate of the base material 10 and the buffer layer 11. Although not shown, a release film or the like may be provided on the side of the energy-ray curable resin film (x) opposite to the buffer layer 11.
[0115] (Third aspect) A third embodiment of the composite sheet of this embodiment is shown in Figure 3. The composite sheet 1c of the third embodiment has an intermediate release layer 13 between the buffer layer 11 and the energy ray curable resin film (x) in the composite sheet of the second embodiment. That is, as shown in Figure 3, the composite sheet 1c of the third embodiment has a base material 10, a buffer layer 11 laminated on one surface 10a of the base material 10, an intermediate release layer 13 laminated on the side of the buffer layer 11 opposite to the base material 10, and an energy ray curable resin film (x) laminated on the side of the intermediate release layer 13 opposite to the buffer layer 11. In the third embodiment, the support sheet is a laminate of the base material 10, the buffer layer 11, and the intermediate release layer 13. Although not shown, a release film or the like may be provided on the side of the energy ray curable resin film (x) opposite to the intermediate release layer 13.
[0116] (buffer layer) As described above, the composite sheet of this embodiment may have a buffer layer between the substrate and the energy-ray curable resin film (x). The buffer layer is a layer that has a buffering effect against forces applied to the buffer layer and layers directly or indirectly adjacent to it. Here, "layers directly or indirectly adjacent to the buffer layer" mainly refers to the energy-ray curable resin film (x) of this embodiment.
[0117] The buffer layer may consist of only one layer or two or more layers. If the buffer layer consists of multiple layers, these layers may be identical or different from each other, and there are no particular limitations on the combination of these layers.
[0118] The thickness of the buffer layer can be adjusted as appropriate according to the height of the protruding electrodes on the surface of the member, but from the viewpoint of making it easier to exert the effects of the present invention even with relatively tall protruding electrodes, it is preferably 150 to 1,000 μm, more preferably 180 to 800 μm, and even more preferably 200 to 600 μm.
[0119] -Storage modulus (G') of the buffer layer at 40°C- In the composite sheet of this embodiment, the storage modulus (G') of the buffer layer at 40°C is preferably 0.08 MPa or higher. If the storage modulus (G') of the buffer layer at 40°C is 0.3 MPa or higher, it becomes easier to ensure the penetration of the protruding electrode by the energy ray curable resin film (x), and thus easier to ensure the reliability of the connection between the chip with the protruding electrode and the substrate. Here, from the viewpoint of making it easier to ensure the penetration of the protruding electrode of the energy ray curable resin film (x), the storage modulus (G') of the buffer layer at 40°C is more preferably 0.5 MPa or more, even more preferably 1 MPa or more, and even more preferably 1.3 MPa or more. Furthermore, the storage modulus (G') of the buffer layer at 40°C is preferably 20 MPa or less, from the viewpoint of ensuring the ability of the energy-ray curable resin film (x) to follow the protruding electrode.
[0120] -Loss tangent (tanδ) of the buffer layer at 40°C- In the composite sheet of this embodiment, the loss tangent (tanδ) of the buffer layer at 40°C is preferably 1.05 or greater. If the loss tangent (tanδ) of the buffer layer at 40°C is 1.05 or higher, it is easier to ensure the embedding ability of the energy-ray-curable resin film (x) into the area around the base of the protruding electrode (penetration of the energy-ray-curable resin film (x) into the area around the base of the protruding electrode). Here, from the viewpoint of making it easier to ensure the embedding of the protruding electrode of the energy ray curable resin film (x), the loss tangent (tanδ) of the buffer layer at 40°C is more preferably 1.07 or higher, even more preferably 1.08 or higher, and even more preferably 1.10 or higher. Furthermore, the loss tangent (tanδ) of the buffer layer at 40°C is preferably 2.00 or less, from the viewpoint of making it easier to adjust the storage modulus (G') of the buffer layer at 40°C to 0.3 or more, thereby making it easier to ensure the penetration of the protruding electrode of the energy ray curable resin film (x).
[0121] The storage modulus (G') and loss tangent (tanδ) of the buffer layer at 40°C can be measured, for example, by the following method. The sample size to be measured is 8 mm in diameter and 1 mm thick (5 layers of 200 μm buffer layers stacked together). Using a rheometer (Anton Paar MCR302), the sample, with the release film removed, is sandwiched between parallel plates from above and below. Shear stress is applied to the sample at a measurement temperature of 0 to 100°C, a gap of 1 mm, a strain of 0.05 to 0.5%, and an angular frequency of 1 Hz, and the shear storage modulus G' and loss tangent tanδ at 40°C are calculated.
[0122] In this embodiment, the storage modulus (G') and loss tangent (tanδ) of the buffer layer at 40°C can be appropriately adjusted by adjusting the composition of the buffer layer, etc. The details of the buffer layer will be explained below, taking into account the method for adjusting the storage modulus (G') and loss tangent (tanδ) of the buffer layer at 40°C.
[0123] -Urethane (meth)acrylate- Urethane (meth)acrylate is a compound having at least a (meth)acryloyl group and a urethane bond, and has the property of polymerizing upon energy ray irradiation. By using urethane (meth)acrylate, flexibility can be provided to the buffer layer, making it easier to adjust the storage modulus (G') and loss tangent (tanδ) of the buffer layer at 40°C to the above range. The urethane (meth)acrylate may be monofunctional or polyfunctional. In this embodiment, polyfunctional urethane (meth)acrylate is preferred, and bifunctional urethane (meth)acrylate is preferred from the viewpoint of easily adjusting the storage modulus (G') and loss tangent (tanδ) of the buffer layer at 40°C to the above range. Urethane (meth)acrylate can be obtained, for example, by reacting a terminal isocyanate urethane prepolymer, which is obtained by reacting a polyol compound with a polyvalent isocyanate compound, with a (meth)acrylate having a hydroxyl group. Note that one or more types of urethane (meth)acrylate may be used. The content of urethane (meth)acrylate in the buffer layer forming composition is preferably 20% by mass or more, more preferably 25% by mass or more, and even more preferably 30% by mass or more, from the viewpoint of easily adjusting the storage modulus (G') and loss tangent (tanδ) of the buffer layer at 40°C to the above range. Furthermore, the content of urethane (meth)acrylate in the buffer layer composition is preferably 70% by mass or less, more preferably 65% by mass or less, and even more preferably 50% by mass or less.
[0124] -Polymerizable monomer- The polymerizable monomer is preferably a polymerizable compound other than the urethane (meth)acrylate mentioned above, and is a compound that can be polymerized with other components by irradiation with energy rays. Specifically, the polymerizable monomer is preferably a compound having at least one (meth)acryloyl group. Examples of polymerizable monomers include (meth)acrylates having alkyl groups with 1 to 30 carbon atoms; (meth)acrylates having functional groups such as hydroxyl groups, amide groups, amino groups, and epoxy groups; (meth)acrylates having an alicyclic structure; (meth)acrylates having an aromatic structure; (meth)acrylates having a heterocyclic structure; and vinyl compounds such as styrene, hydroxyethyl vinyl ether, hydroxybutyl vinyl ether, N-vinylformamide, N-vinylpyrrolidone, and N-vinylcaprolactam. Examples of (meth)acrylates having alkyl groups with 1 to 30 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, and eicosyl (meth)acrylate. Examples of functional group-containing (meth)acrylates include hydroxyl group-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N-butyl (meth)acrylamide, and N-methylol (meth)acrylamide. Examples include amide group-containing compounds such as lylamide, N-methylolpropane(meth)acrylamide, N-methoxymethyl(meth)acrylamide, and N-butoxymethyl(meth)acrylamide; amino group-containing (meth)acrylates such as primary amino group-containing (meth)acrylates, secondary amino group-containing (meth)acrylates, and tertiary amino group-containing (meth)acrylates; and epoxy group-containing (meth)acrylates such as glycidyl(meth)acrylate, methylglycidyl(meth)acrylate, and allylglycidyl ether. Examples of (meth)acrylates having an alicyclic structure include isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyloxy (meth)acrylate, cyclohexyl (meth)acrylate, trimethylcyclohexyl (meth)acrylate, and adamantane (meth)acrylate. Examples of (meth)acrylates having an aromatic structure include phenylhydroxypropyl (meth)acrylate, benzyl (meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate. Examples of (meth)acrylates having a heterocyclic structure include tetrahydrofurfuryl(meth)acrylate and morpholine(meth)acrylate. In this embodiment, the polymerizable monomer preferably includes (meth)acrylates having alkyl groups with 1 to 30 carbon atoms and (meth)acrylates having an alicyclic structure. From the viewpoint of easily adjusting the storage modulus (G') and loss tangent (tanδ) of the buffer layer at 40°C to the above range, (meth)acrylates having alkyl groups with 4 to 14 carbon atoms are preferred, and as (meth)acrylates having an alicyclic structure, isobornyl (meth)acrylate and trimethylcyclohexyl (meth)acrylate are preferred. Furthermore, if a buffer layer-forming composition contains a crosslinking agent, (meth)acrylates having functional groups that can react with the crosslinking agent are undesirable. This is because the crosslinked structure formed by the crosslinking reaction may increase the residual stress in the buffer layer. For example, a buffer layer-forming composition containing a polyisocyanate-based crosslinking agent and a (meth)acrylate having hydroxyl groups is undesirable. The content of polymerizable monomers in the buffer layer forming composition is preferably 20% by mass or more, and more preferably 30% by mass or more, from the viewpoint of easily adjusting the storage modulus (G') and loss tangent (tanδ) of the buffer layer at 40°C to the above range. Furthermore, the content of polymerizable monomers in the buffer layer forming composition is preferably 80% by mass or less, and more preferably 70% by mass or less. Furthermore, the mass ratio of urethane (meth)acrylate to polymerizable monomer (urethane (meth)acrylate / polymerizable monomer) in a total of 100 parts by mass of urethane (meth)acrylate and polymerizable monomer is preferably 20 / 80 to 80 / 20, and more preferably 30 / 70 to 70 / 30, from the viewpoint of easily adjusting the storage modulus (G') and loss tangent (tanδ) of the buffer layer at 40°C to the above range.
[0125] -Photopolymerization initiator- When the buffer layer forming composition contains the above-mentioned urethane (meth)acrylate and polymerizable monomer, it is preferable that the buffer layer forming composition also contains a photopolymerization initiator. By including a photopolymerization initiator, polymerization proceeds reliably, and the storage modulus (G') and loss tangent (tanδ) of the buffer layer at 40°C can be easily adjusted to the above range. Examples of photopolymerization initiators include benzoin compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, thioxanthone compounds, and peroxide compounds, as well as photosensitizers such as amines and quinones. Specifically, examples include 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and 2,2-dimethoxy-1,2-diphenylethane-1-one. These photopolymerization initiators may be used individually or in combination of two or more. The amount of photopolymerization initiator added is preferably 0.05 parts by mass or more and 15 parts by mass or less, and more preferably 0.5 parts by mass or more and 10 parts by mass or less, based on 100 parts by mass of the total of urethane (meth)acrylate and polymerizable monomer.
[0126] -Chain Transfer Agent- The buffer layer forming composition preferably contains a chain transfer agent. The chain transfer agent can induce a chain transfer reaction and regulate the progress of the curing reaction of the buffer layer forming composition. By including a chain transfer agent, components with relatively short molecular chains can remain even after curing, so the cured polymer has a relatively flexible structure. As a result, the storage modulus (G') and loss tangent (tanδ) of the buffer layer at 40°C can be easily adjusted to the above range. Examples of chain transfer agents include thiol group-containing compounds. Examples of thiol group-containing compounds include nonyl mercaptan, 1-dodecanethiol, 1,2-ethanedithiol, 1,3-propanedithiol, triazinethiol, triazinedithiol, triazinetrithiol, 1,2,3-propanetrithiol, tetraethylene glycol-bis(3-mercaptopropionate), trimethylolpropanetris(3-mercaptopropionate), pentaerythritoltetrakis(3-mercaptopropionate), and pentaerythritol. Examples include thritol tetrakisthioglucolate, dipentaerythritol hexakis(3-mercaptopropionate), tris[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, 1,4-bis(3-mercaptobutyryloxy)butane, pentaerythritol tetrakis(3-mercaptobutyrate), and 1,3,5-tris(3-mercaptobutyloxyethyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione. The chain transfer agent may be used individually or in combination of two or more types. From the viewpoint of easily adjusting the storage modulus (G') and loss tangent (tanδ) of the buffer layer at 40°C to the above range, the amount of chain transfer agent blended is preferably 1.0 to 2.5 parts by mass, more preferably 1.2 to 2.0 parts by mass, and even more preferably 1.3 to 1.8 parts by mass, per 100 parts by mass of the total of urethane (meth)acrylate and polymerizable monomer.
[0127] -Other ingredients- The buffer layer may contain other components. These other components are not particularly limited and can be appropriately selected depending on the purpose.
[0128] -Preparation of a buffer layer- As a composition for forming a buffer layer, for example, a buffer layer-forming composition containing the above-mentioned components, or a composition obtained by diluting the buffer layer-forming composition with a solvent or the like, can be prepared. Examples of solvents include organic solvents such as methyl ethyl ketone, acetone, ethyl acetate, tetrahydrofuran, dioxane, cyclohexane, n-hexane, toluene, xylene, n-propanol, and isopropanol. Then, a buffer layer-forming composition or the like is applied to a release film or substrate by a known method such as spin coating, spray coating, bar coating, knife coating, roll coating, blade coating, die coating, or gravure coating to form a coating film, and this coating film is cured to form a buffer layer on the substrate. In this embodiment, it is preferable to cure the coating film by irradiation with energy rays. Examples of energy rays include ultraviolet rays and electron beams, with ultraviolet rays being preferred. Furthermore, in this embodiment, it is preferable to cure the coating film by irradiating it with energy rays multiple times. By doing so, the degree of curing of the buffer layer can be controlled, and the storage modulus (G') and loss tangent (tanδ) of the buffer layer at 40°C can be easily adjusted to the above range. If the energy source is ultraviolet light, the ultraviolet irradiation conditions are preferably such that the ultraviolet irradiance is 30-500 mW / cm². 2 More preferably 50-340 mW / cm² 2 The ultraviolet radiation dose (cumulative light dose) is preferably 100 to 2,500 mJ / cm². 2 More preferably 150 to 2,000 mJ / cm² 2 That is the case. When irradiating with ultraviolet light multiple times, it is preferable that the illuminance and irradiation dose are greater than those of the previous irradiation. Alternatively, the coated film may be exposed to oxygen and irradiated with energy rays, and then the coated film may be shielded from oxygen and irradiated with energy rays again.
[0129] (Intermediate delamination layer) As described above, the composite sheet of this embodiment may have an intermediate release layer between the buffer layer and the energy ray curable resin film (x). The intermediate release layer is provided to easily peel off the buffer layer from the energy ray curable resin film (x) after the energy ray curable resin film (x) has been attached to the protruding electrode forming surface of the member with protruding electrodes by attaching the composite sheet to the protruding electrode forming surface.
[0130] The intermediate delamination layer is in the form of a sheet or film, and its constituent material is not particularly limited. The intermediate delamination layer preferably contains ethylene-vinyl acetate copolymer (EVA). The intermediate peeling layer may contain other components besides those mentioned above. These other components are not particularly limited and can be appropriately selected depending on the purpose.
[0131] The interdebris layer may be a single layer or a multi-layer structure of two or more layers. If the interdebris layer consists of multiple layers, these layers may be identical or different from each other, and there are no particular limitations on the combination of these layers.
[0132] The thickness of the interlayer is not particularly limited, but is preferably 5 to 30 μm, more preferably 6 to 25 μm, and even more preferably 7 to 20 μm.
[0133] (base material) The base material is in the form of a sheet or film, and its constituent materials include, for example, the following various resins. Examples of resins constituting the base material include polyethylene such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and high-density polyethylene (HDPE); polyolefins other than polyethylene such as polypropylene, polybutene, polybutadiene, polymethylpentene, and norbornene resin; ethylene-based copolymers such as ethylene-vinyl acetate copolymer, ethylene-(meth)acrylic acid copolymer, ethylene-(meth)acrylic acid ester copolymer, and ethylene-norbornene copolymer (polymers obtained using ethylene as a monomer); and vinyl chloride-based resins such as polyvinyl chloride and vinyl chloride copolymer (using vinyl chloride as a monomer). Examples of resins obtained from this process include: polystyrene; polycycloolefin; polyesters such as polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polyethylene isophthalate, polyethylene-2,6-naphthalenedicarboxylate, and all aromatic polyesters having aromatic cyclic groups as all constituent units; copolymers of two or more of the above polyesters; poly(meth)acrylic acid esters; polyurethane; polyurethane acrylate; polyimide; polyamide; polycarbonate; fluororesin; polyacetal; modified polyphenylene oxide; polyphenylene sulfide; polysulfone; polyether ketone; and the like. Furthermore, examples of resins constituting the base material include polymer alloys such as mixtures of the above-mentioned polyester and other resins. It is preferable that the polymer alloy of polyester and other resins contains a relatively small amount of the resin other than polyester. Furthermore, examples of resins constituting the base material include crosslinked resins obtained by crosslinking one or more of the above-mentioned resins; and modified resins such as ionomers using one or more of the above-mentioned resins. The resins that make up the base material may be used individually or in combination of two or more types.
[0134] The base material may consist of only one layer or two or more layers. If the base material consists of multiple layers, these layers may be identical or different from each other, and there are no particular limitations on the combination of these layers.
[0135] The thickness of the substrate is not particularly limited, but is preferably 5 to 1,000 μm, more preferably 10 to 500 μm, even more preferably 15 to 300 μm, and even more preferably 20 to 150 μm.
[0136] The base material is preferably one with high thickness accuracy, that is, one in which thickness variation is suppressed regardless of the location. Among the constituent materials mentioned above, examples of materials with high thickness accuracy that can be used to construct such a base material include polyethylene, polyolefins other than polyethylene, polyethylene terephthalate, polybutylene terephthalate, polyesters other than polyethylene terephthalate and polybutylene terephthalate, and ethylene-vinyl acetate copolymers.
[0137] In addition to the main constituent materials such as the resin mentioned above, the base material may also contain various known additives such as fillers, colorants, antioxidants, organic lubricants, catalysts, and plasticizers.
[0138] The substrate may be transparent or opaque, may be colored depending on the purpose, or may have other layers deposited on it.
[0139] The substrate can be manufactured by known methods. For example, a substrate containing a resin can be manufactured by molding a resin composition containing the above-mentioned resin.
[0140] (Method of manufacturing composite sheets) The composite sheet of this embodiment can be manufactured by sequentially stacking the above-mentioned layers in corresponding positional relationships. For example, a composite sheet having a laminated structure of a substrate and an energy-ray curable resin film (x) can be manufactured by the method shown below. The energy-curable resin composition (x1) of this embodiment is applied to the release surface of the release film, and dried as necessary to form an energy-curable resin film (x) on the release film. Next, the substrate and the exposed surface of the energy-ray-curable resin film (x) opposite to the release film are bonded together. This yields a composite sheet having a laminated structure of the substrate and the energy-ray-curable resin film (x). This composite sheet exhibits excellent adhesion when the height of the protruding electrode is 150 μm or less, and even better adhesion when it is 80 μm or less. The release film provided on the energy-ray curable resin film (x) in the composite sheet can be removed at any stage between the time of manufacture of the composite sheet and the time of use. Furthermore, a composite sheet having a laminated structure of a substrate and an energy-ray curable resin film (x) can also be manufactured by coating one side of the substrate with an energy-ray curable resin composition (x1) and drying it as necessary.
[0141] Furthermore, for example, a composite sheet having a substrate, a buffer layer, and an energy-ray curable resin film (x) in this order can be manufactured by the method shown below. A buffer layer-forming composition is applied to the release surface of the release film and dried to form a buffer layer on the release film. Then, the side of the buffer layer that is not in contact with the release film is bonded to the substrate to obtain a laminate (first laminated sheet) in which the substrate, buffer layer, and release film are stacked in this order. Separately, the energy ray-curable resin composition (x1) of this embodiment is applied to the release surface of the release film, and dried as necessary to form an energy ray-curable resin film (x) on the release film. Next, after removing the release film from the first laminated sheet, the exposed surface of the buffer layer opposite to the substrate is bonded to the exposed surface of the energy-ray curable resin film (x) opposite to the release film. This yields a composite sheet having a laminated structure of a substrate, a buffer layer, and an energy-ray curable resin film (x). The release film provided on the energy-ray curable resin film (x) in the composite sheet can be removed at any stage between the time of manufacture of the composite sheet and the time of use.
[0142] A composite sheet comprising layers other than those described above can be manufactured by adding or omitting steps as appropriate in the manufacturing method described above, so that the stacking positions of each layer are at desired positions.
[0143] [Details of the manufacturing method of the semiconductor manufacturing apparatus of this embodiment] The method for manufacturing the semiconductor device of this embodiment will be described below with reference to the drawings.
[0144] The method for manufacturing a semiconductor device according to this embodiment includes the step of forming a protective film on the protruding electrode formation surface of a member with protruding electrodes (for example, a semiconductor wafer with protruding electrodes) using an energy-ray curable resin film or an energy-ray curable resin film composite sheet. In this embodiment, the member with the protruding electrode is not particularly limited, but examples include semiconductor wafers and semiconductor chips equipped with the protruding electrode. Here, taking the case where the member with protruding electrodes is a semiconductor wafer with bumps and the surface on which the protruding electrodes are formed as an example, the manufacturing method of the semiconductor device according to this embodiment is preferably a manufacturing method that includes the following steps 1 to 5. Step 1: The process of attaching the energy-curable resin film (x) of the energy-curable resin film composite sheet of this embodiment to the protruding electrode formation surface of a semiconductor wafer, causing the tops of the protruding electrodes to protrude from the energy-curable resin film, thereby laminating the energy-curable resin film composite sheet onto the semiconductor wafer (hereinafter also referred to as the "attachment step"). Step 2: A step to remove layers other than the energy-ray curable resin film (x) from the energy-ray curable resin film composite sheet laminated in Step 1 (hereinafter also referred to as the "removal step"). Step 3: A step to form a cured resin film by curing an energy ray curable resin film (x) on a semiconductor wafer (hereinafter also referred to as the "curing step"). Step 4: A step to manufacture semiconductor chips by dividing the semiconductor wafer after Step 3 (hereinafter also referred to as the "dividing step"), and a step to cut the cured resin film after Step 3 (hereinafter also referred to as the "cutting step"). Step 5: The process of mounting the semiconductor chip with the cured resin film onto the substrate using a flip-chip connection (hereinafter also referred to as the "mounting process"). The following explains each step with reference to the diagrams. In the following explanation, we will use the case where composite sheet 1c is used as an example, but of course, composite sheet 1a or 1b may also be used, or the energy ray curable resin film (x) may be directly attached as a single layer. Furthermore, although bumps will be used as an example of protruding electrodes in the following explanation, other types of protruding electrodes may, of course, be used in this invention.
[0145] <Step 1: Pasting Process> Figure 4 is a schematic cross-sectional view illustrating the application process. Figures 4(a) and (b) show the process of attaching an energy-ray curable resin film composite sheet 1c to the bump-forming surface 20a of a semiconductor wafer 20. In the bonding process, for example, first, as shown in Figure 4(a), the composite sheet 1c is positioned so that the energy-curable resin film (x) faces the bump-forming surface 20a of the semiconductor wafer 20. Next, the energy-curable resin film (x) is brought into contact with the bumps 21 on the semiconductor wafer 20, and the composite sheet 1c is pressed against the semiconductor wafer 20. By pressing, the energy-curable resin film (x) is sequentially pressed onto the surface of the bumps 21 and the bump-forming surface 20a of the semiconductor wafer 20. As shown in Figure 4(a), when the composite sheet 1c is pressed onto the semiconductor wafer 20, the energy-ray curable resin film (x) is subjected to pressure from the bumps 21 through the buffer layer 11, causing tearing in the energy-ray curable resin film (x). Finally, as shown in Figure 4(b), the top of the bump 21 protrudes through the energy-ray curable resin film (x). Furthermore, from the viewpoint of ensuring that the top of the bump 21 protrudes through the energy-curable resin film (x), as described above, it is preferable that the storage modulus (G') of the buffer layer at 40°C be 0.10 MPa or higher. Also, from the viewpoint of improving bump embedding performance, as described above, it is preferable that the loss tangent (tanδ) of the buffer layer at 40°C be 1.05 or higher.
[0146] The height of the bump 21 is not particularly limited, but is preferably 120 to 300 μm, more preferably 150 to 270 μm, and even more preferably 180 to 240 μm. Furthermore, bumps with relatively low heights may be used. In this case as well, the height of the bump 21 is not particularly limited, but is preferably 5 to 150 μm, more preferably 10 to 80 μm, and even more preferably 20 to 50 μm. In this specification, "bump height" means the height of the bump at the highest point of the bump from the bump-forming surface.
[0147] The width of the bump 21 is not particularly limited, but is preferably 170 to 350 μm, more preferably 200 to 320 μm, and even more preferably 230 to 290 μm. In this specification, "bump width" means the maximum length of a line segment obtained by drawing a straight line between two different points on the bump surface when the bump is viewed from above in a plan view from a direction perpendicular to the bump-forming surface.
[0148] The distance between adjacent bumps 21 is not particularly limited, but is preferably 250 to 800 μm, more preferably 300 to 600 μm, and even more preferably 350 to 500 μm. In this specification, "distance between adjacent bumps" means the minimum distance between the surfaces of adjacent bumps.
[0149] As a method for pressing the composite sheet 1c onto the semiconductor wafer 20, known methods for pressing and attaching various sheets to an object can be applied, such as using a roller-type laminator. The temperature at which the composite sheet 1c is pressed onto the semiconductor wafer 20 is not particularly limited and may be, for example, 20 to 60°C, and preferably 30 to 50°C. The pressure applied when pressing the composite sheet 1c onto the semiconductor wafer 20 is not particularly limited and may be, for example, 0.1 to 1.5 MPa, and preferably 0.3 to 1 MPa. The speed at which the composite sheet 1c is attached to the semiconductor wafer 20 is not particularly limited, and is usually around 2-3 mm / s.
[0150] After the bonding process, the side of the semiconductor wafer 20 opposite to the bump-forming surface 20a (the back surface) may be ground as needed, and further, another energy-ray curable resin film composite sheet (not shown) may be bonded to the back surface after grinding.
[0151] <Step 2: Removal step> Figure 5 is a schematic cross-sectional view illustrating the removal process. After the bonding process, as shown in Figure 5, layers other than the energy-ray curable resin film (x) are removed from the composite sheet 1c to obtain a semiconductor wafer 30 with an energy-ray curable resin film, which comprises a semiconductor wafer 20 and an energy-ray curable resin film (x) provided on the bump-forming surface 20a of the semiconductor wafer 20. Layers other than the energy-ray curable resin film (x) can be removed by known methods.
[0152] <Process 3: Curing process> Figure 6 is a schematic cross-sectional view illustrating the curing process. After the removal process, as shown in Figure 6, the energy-ray curable resin film (x) is cured by irradiation with energy rays to form a cured resin film (x)' on the bump-forming surface 20a of the semiconductor wafer 20, which is formed by the energy-ray curing of the energy-ray curable resin film (x). This results in a semiconductor wafer 40 with a cured resin film (x)' on the bump-forming surface 20a of the semiconductor wafer 20. The conditions for curing the energy-ray-curable resin film (x) with energy rays are not particularly limited and can be appropriately adjusted and determined depending on the type of material constituting the energy-ray-curable resin film (x). For example, the illuminance of the energy rays during the energy ray curing of an energy ray-curable resin film (x) is 60-320 mW / cm². 2 It is preferable that the total energy ray intensity during curing is 100 to 1000 mJ / cm². 2 It is preferable that this be the case. Furthermore, the atmosphere during energy ray curing is not particularly limited and can be appropriately adjusted and determined according to the type of material constituting the energy ray curable resin film (x), but it is preferable to carry it out under an inert gas atmosphere such as nitrogen gas.
[0153] <Process 4: Splitting process, cutting process> Figure 7 is a schematic cross-sectional view illustrating the dividing and cutting processes. After the curing process, as shown in Figure 7, the semiconductor wafer 20 is divided in the splitting process to produce a semiconductor chip 50. In the cutting process, the cured resin film (x)' is cut to form the cured resin film (x0)' after cutting. This results in a semiconductor chip 60 with a cured resin film, having the cured resin film (x0)' after cutting on the bump-forming surface of the semiconductor chip 50.
[0154] The dividing and cutting processes can be carried out by known methods. The order in which the dividing and cutting processes are performed is not particularly limited, but it is preferable to perform the dividing and cutting processes simultaneously or in that order. When the dividing and cutting processes are performed in this order, for example, the dividing process may be performed by a known dicing method, and then the cutting process may be performed immediately afterward. Dicing can be performed by providing a dicing sheet (not shown) on the back surface of the semiconductor wafer 20 (which may be the back surface after grinding). In the cutting process, the cured resin film (x)' is cut along the planned or already divided portion of the semiconductor wafer 20 (in other words, the outer periphery of the semiconductor chip 50).
[0155] <Process 5: Assembly Process> In the mounting process, the semiconductor chip with the protective film obtained in the curing process is flip-chip connected to the electrodes (wirings) of the substrate at the top of the bump (not shown). At this time, the semiconductor chip with the protective film is connected to the circuit formation surface of the substrate. [Examples]
[0156] The present invention will be specifically described by the following examples, but the present invention is not limited to these examples. If the measuring instruments used in the examples are difficult to obtain due to discontinuation or other reasons, measurements can be taken using other instruments with equivalent performance.
[0157] [Manufacturing of composite sheets comprising an energy-ray curable resin film (x)] A composite sheet comprising an energy-curable resin film (x) was manufactured by the method described below.
[0158] <Raw materials for energy ray curable resin composition (x1)> The raw materials used in the production of the energy ray-curable resin composition (x1) are shown below. "Polymer component (A)" (A)-1: An acrylic polymer obtained by copolymerizing butyl acrylate (33 parts by mass), methyl acrylate (27 parts by mass), N-acryloylmorpholine (25 parts by mass), and 2-hydroxyethyl acrylate (15 parts by mass) was reacted with 2-methacryloyloxyethyl isocyanate (MOI) so as to add to 90 mol% of the total hydroxyl groups of the acrylic polymer to obtain an energy-ray curable acrylic polymer (weight-average molecular weight: 15,000, glass transition temperature: 2°C). (A)-2: Butyl acrylate (33 parts by mass), methyl acrylate (27 parts by mass), N-acryloylmorpholine (25 parts by mass), and 2-hydroxyethyl acrylate (15 parts by mass) were copolymerized to obtain an acrylic polymer (weight-average molecular weight: 15,000, glass transition temperature: 2°C). (A)-3: An acrylic polymer was obtained by copolymerizing butyl acrylate (33 parts by mass), methyl acrylate (27 parts by mass), N-acryloylmorpholine (25 parts by mass), and 2-hydroxyethyl acrylate (15 parts by mass). 2-methacryloyloxyethyl isocyanate (MOI) was then reacted with the copolymer to add to 90 mol% of the total hydroxyl groups of the acrylic polymer, thereby obtaining an acrylic polymer (weight-average molecular weight: 200,000, glass transition temperature: 2°C). (A)-4: Urethane acrylate (Quick cure 8100EA70, manufactured by KJ Chemicals, weight-average molecular weight: 10,000, glass transition temperature: 12℃). (A)-5: An acrylic polymer was obtained by copolymerizing butyl acrylate (33 parts by mass), methyl acrylate (27 parts by mass), N-acryloylmorpholine (25 parts by mass), and 2-hydroxyethyl acrylate (15 parts by mass). 2-methacryloyloxyethyl isocyanate (MOI) was then reacted with the copolymer to add 2-methacryloyloxyethyl isocyanate (MOI) to 90 mol% of the total hydroxyl groups of the acrylic polymer, thereby obtaining an acrylic polymer (weight-average molecular weight: 8,000, glass transition temperature: 2°C). (A)'-1: An acrylic polymer was obtained by copolymerizing butyl acrylate (33 parts by mass), methyl acrylate (27 parts by mass), N-acryloylmorpholine (25 parts by mass), and 2-hydroxyethyl acrylate (15 parts by mass). 2-methacryloyloxyethyl isocyanate (MOI) was then reacted with the copolymer to add to 90 mol% of the total hydroxyl groups of the acrylic polymer, thereby obtaining an acrylic polymer (weight-average molecular weight: 400,000, glass transition temperature: 2°C). "Compound component (B)" (B)-1: ε-Caprolactone-modified tris-(2-acryloxyethyl) isocyanurate ("NK Ester A-9300-1CL" manufactured by Shin Nakamura Chemical Industry Co., Ltd.), polystyrene equivalent value in GPC, number average molecular weight 321) (B)-2: Liquid modified bisphenol A type epoxy resin (DIC Corporation's "Epiclon EXA-4850-150", number average molecular weight 900, epoxy equivalent 450 g / eq) (B)-3: Dicyclopentadiene type epoxy resin (DIC Corporation's "Epiclon HP-7200HH", weight-average molecular weight 1,000, epoxy equivalent 254-264 g / eq) "Photopolymerization initiator (C)" (C)-1:2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone (IGM Resins "Omnirad 379") "Photoacid generator (D1)" (D)-1: Sulfonium salt type photoacid generator (SunApro Co., Ltd. "CPI-100P") "Filling material (E)" (E)-1: Spherical silica modified with epoxy groups (Admanano YA050C-MKK, manufactured by Admatex, with an average particle size of 50 nm) "Thermosetting agent (G)" (G)-1:2-phenyl-4,5-dihydroxymethylimidazole (Shikoku Chemicals Co., Ltd. "Curesol 2PHZ-PW") "Thermosetting catalyst (H)" (H)-1: Dicyandiamide (DICY7, manufactured by Mitsubishi Chemical Corporation)
[0159] <Manufacturing Example 1: Preparation of Energy Ray Curable Resin Film (x)-1 and Composite Sheet (X)-1> (Preparation of energy ray curable resin film (x)-1) By blending the raw materials shown in Table 1, dissolving or dispersing them in methyl ethyl ketone, and stirring at 23°C, an energy-ray curable resin composition was obtained in which the total concentration of all components other than the solvent was 45% by mass. Note that all amounts of components other than the solvent shown here represent the amounts of the target product excluding the solvent. Also, in Table 1, the unit of each component amount is "parts by mass". Next, using a polyethylene terephthalate-based release film (Lintec Corporation, SP-PET381031, 38 μm) as the release film, the energy-ray curable resin composition obtained above was coated onto the release surface and dried at 100°C for 2 minutes to produce an energy-ray curable resin film (x)-1 with a thickness of 30 μm.
[0160] (Preparation of a buffer layer) Composition A1 for forming a buffer layer was obtained by blending 40 parts by mass of aliphatic urethane acrylate (CN966J75 NS, manufactured by Arkema), 40 parts by mass of isobornyl acrylate (IBXA), and 20 parts by mass of dodecyl acrylate, totaling 100 parts by mass, with 3.0 parts by mass of a photopolymerization initiator (Irgacure 1173 (2-hydroxy-2-methyl-1-phenyl-propan-1-one), manufactured by BASF) and 1.5 parts by mass of a chain transfer agent (Kalenz MT PE1 (pentaerythritol tetrakis (3-mercaptobutyrate)), manufactured by Resonaq). The buffer layer-forming composition was applied to one side of a polyethylene terephthalate film (Toray Industries, Ltd., "Polyester Film "Lumirror" U34", 75 μm thick) using a knife method to form a buffer layer-forming composition layer with a thickness of 400 μm. Next, the formed buffer layer-forming composition layer was laminated with a PET release film (Lintec Corporation, SP-PET381130, 38 μm thick) to shield the buffer layer-forming composition layer from oxygen. Subsequently, an illuminance of 80 mW / cm² was applied using a high-pressure mercury lamp. 2 , integrated light intensity 200 mJ / cm 2 After UV irradiation under these conditions, a metal halide lamp was used to achieve an illuminance of 330 mW / cm². 2 , irradiation amount 1260mJ / cm 2By irradiating with ultraviolet light under these conditions, the buffer layer-forming composition layer was cured to form a buffer layer with a thickness of 400 μm. As a result, a laminated sheet (hereinafter also referred to as the "first laminated sheet") was obtained, in which the base material, the buffer layer, and the release film were laminated in this order in the thickness direction.
[0161] (Preparation of the intermediate delamination layer) At room temperature, an ethylene-vinyl acetate copolymer (weight-average molecular weight 55,000, VA content 20% by mass) was dissolved in toluene to prepare a toluene solution with a solid content concentration of 12% by mass, which was used as the composition for forming the intermediate peel layer. Then, the intermediate release layer formation composition obtained above was applied to the release treatment surface of a newly prepared release film (Lintec Corporation, product name "SP-PET381031", thickness 38 μm), and heated and dried at 100°C for 2 minutes to form an intermediate release layer with a thickness of 10 μm.
[0162] (Creation of composite sheets) In the first laminated sheet obtained above, the release film was removed, and the exposed surface of the intermediate release layer obtained above was bonded to the exposed surface of the buffer layer resulting from this process, thereby obtaining a laminated sheet in which an intermediate release layer was further laminated. Next, the release film was removed from the intermediate release layer after lamination, and the exposed surface of the energy-curable resin film (x)-1 with a single-sided release film obtained above was laminated to the exposed surface of the intermediate release layer. As a result, a composite sheet (X)-1 was obtained, consisting of a substrate (thickness 75 μm), a buffer layer (thickness 400 μm), an intermediate release layer (thickness 10 μm), and an energy-curable resin film (x)-1 (thickness 30 μm) laminated in this order in the thickness direction.
[0163] <Manufacturing Examples 2-5: Preparation of Energy Ray Curable Resin Films (x)-2-5 and Composite Sheets (X)-2-5> Except for changing the proportions of each raw material as shown in Table 1, energy-curable resin films (x)-2 to 5 with a thickness of 30 μm and composite sheets (X)-2 to 5 comprising energy-curable resin films (x)-2 to 5 were prepared using the same method as in Production Example 1.
[0164] <Comparative Manufacturing Examples 1-2: Fabrication of Energy Ray Curable Resin Films (x)-1'-2' and Composite Sheets (X)-1'-2'> Except for changing the proportions of each raw material as shown in Table 1, energy-curable resin films (x)-1'~2' with a thickness of 30 μm and composite sheets (X)-1'~2' comprising energy-curable resin films (x)-1'~2' were prepared using the same method as in Production Example 1.
[0165] <Comparative Manufacturing Example 3: Preparation of Thermosetting Resin Film (x)-3' and Composite Sheet (X)-3'> Except for changing the proportions of each raw material as shown in Table 1, a thermosetting resin film (x)-3' with a thickness of 30 μm and a composite sheet (X)-3' comprising the thermosetting resin film (x)-3' were prepared using the same method as in Production Example 1.
[0166] [Measurement method] The storage modulus (E'1) at 40°C before curing of the energy-ray curable resin films (x)-1 to (x)-5 and (x)-1' to (x)-2', and the thermosetting resin film (x)-3', was measured by the method described below.
[0167] <Storage modulus (E'1) at 40°C before hardening> Multiple energy-ray curable resin films (x)-1 with a thickness of 40 μm were prepared using the same method as in Manufacturing Example 1. Next, by removing the release films from these films and bonding the exposed surfaces of the energy-ray curable resin films (x)-1 together, a test specimen (cured resin film-forming film test specimen, thickness 200 μm, length 30 mm and width 4 mm in the tensile direction in the tensile mode described later) was prepared. Next, using a dynamic viscoelasticity automatic measuring device (A&D Corporation's "Leovibron DDV-01GP"), the storage modulus E' was measured in the temperature range from -10°C to 140°C under the following measurement conditions: tensile method (tensile mode), chuck distance: 20 mm, frequency: 11 Hz, heating rate: 3°C / min, and constant heating rate. The above measurements were also performed on the energy-curable resin films (x)-2 to (x)-5 and (x)-1' to (x)-2', as well as the thermosetting resin film (x)-3'.
[0168] The results of each measurement are shown in Table 2.
[0169] [Examples 1-5 and Comparative Examples 1-3] In Examples 1-5 and Comparative Examples 1-3, the composite sheet (X) shown in Table 1 was used, and the evaluation described later was performed.
[0170] <Width of seepage of energy ray-curable resin film> An energy-ray curable resin film (x)-1 with a thickness of 30 μm was prepared using the same method as in Manufacturing Example 1. The release surface of another release film (Lintec Corporation, product name "SP-PET381031", thickness 38 μm) was bonded to the exposed surface of the energy-ray curable resin film (x)-1. This resulted in a laminate in which the energy-ray curable resin film was sandwiched between the release films. A roll was fabricated by winding 50m of the aforementioned laminate onto a core. The roll was then left standing vertically for two weeks under 30°C conditions, and the maximum width of the energy-ray curable resin film seeping from the end of the roll was measured to determine the amount of seepage. The above measurements were similarly performed using energy-ray curable resin films (x)-2 to (x)-5 and (x)-1' to (x)-2', as well as thermosetting resin film (x)-3'.
[0171] <Presence or absence of air bubbles when applied> A roller-type laminator (Lintec Corporation, product name "RAD-3520 F / 12") was used as the lamination device, and under the following lamination conditions, the surface of the energy-ray curable resin film (x)-1 of the composite sheet (X)-1 was attached to the protruding electrode formation surface of a semiconductor wafer having protruding electrodes, and the support sheet (a laminate of the substrate, buffer layer, and intermediate release layer) was peeled off. (Attachment conditions) • Table temperature: 40°C ·Application speed: 3mm / s • Adhesion pressure: 0.5 MPa Roller application height: 400 μmt (Specifications of semiconductor wafers with protruding electrodes) • Wafer size: 8 inches • Wafer thickness: 200 μm • Height of the protruding electrode: 210 μm • Width of the protruding electrode: 250 μm ·Distance between protruding electrodes: 400μm Then, the surface of the semiconductor wafer with protruding electrodes was observed through the cured resin film using a digital microscope (Keyence Corporation, model name "VHX-7000") at a magnification of 100x. For 100 protruding electrodes, the presence or absence of air bubbles between the vertical and horizontal protruding electrodes was also observed. Then, the presence or absence of air bubbles during application was evaluated according to the following criteria. Evaluation A: No bubble connections have formed between the vertical and horizontal protruding electrodes. Evaluation B: Of the total number of locations between observed protruding electrodes, the number of locations where bubble connections occurred was greater than 0% and less than or equal to 20%. Evaluation C: Of the total number of locations observed between the protruding electrodes, more than 20% were locations where bubble connections occurred. The above evaluation was carried out similarly using composite sheets (X)-2 to (X)-5 and composite sheets (X)-1' to (X)-3'.
[0172] In each evaluation, a rating of A or B was considered a pass, and a rating of C was considered a fail.
[0173] The measurement and evaluation results are shown in Table 2.
[0174]
Table 1
[0175]
Table 2
[0176] From Table 1, it is found that in Examples 1 to 5, where the energy ray-curable resin film (x) comprises a polymer component (A) which is a polymer having a weight average molecular weight of 5,000 or more, and a compound component (B) which is a compound having an energy ray-curable group and a weight average molecular weight of less than 5,000, and the polymer component (A) further comprises an acrylic resin (A1) having a weight average molecular weight (Mw) of 5,000 to 250,000, the exudation during standing can be suppressed while the generation of air bubbles during lamination can be suppressed. In addition, the energy ray-curable resin film usually does not require heating at a high temperature and can be cured in a short time. On the other hand, it is found that in Comparative Examples 1 to 3, where the energy ray-curable resin film (x) or the thermosetting resin film does not contain the acrylic resin (A1) having a weight average molecular weight (Mw) of 5,000 to 250,000, the generation of air bubbles during lamination cannot be suppressed. In addition, the thermosetting resin film requires heating at a high temperature for a long time to be cured.
Description of Symbols
[0177] (x) Energy ray-curable resin film (x)' Cured resin film 1a, 1b, 1c Composite sheet 10 Base material 10a One surface of the base material 11 Buffer layer 13 Intermediate release layer 20 Semiconductor wafer 20a Bump-forming surface of semiconductor wafer 21 Bump (protruding electrode) 30 Semiconductor wafer with energy ray-curable resin film 40 Semiconductor wafer with cured resin film 50 semiconductor chips 60 Semiconductor chips with cured resin film
Claims
1. An energy-ray curable resin film for forming a protective film on the protruding electrode forming surface of a member with a protruding electrode, comprising a polymer component (A) which is a polymer with a weight-average molecular weight of 5,000 or more, and a compound component (B) which is a compound having an energy-ray curable group and a weight-average molecular weight of less than 5,000, The polymer component (A) comprises an acrylic resin (A1) having a weight-average molecular weight (Mw) of 5,000 or more and 250,000 or less, and the compound component (B) comprises a radical polymerizable energy ray curable compound (B1) having a weight-average molecular weight of less than 5,000, wherein the energy ray curable resin film is provided.
2. Furthermore, the energy ray curable resin film according to claim 1, comprising a photopolymerization initiator (C).
3. The energy ray curable resin film according to claim 1 or 2, wherein the radical polymerizable energy ray curable compound (B1) includes an acrylate-based compound.
4. An energy-ray curable resin film composite sheet comprising a support sheet and an energy-ray curable resin film according to claim 1 or 2.
5. A method for manufacturing a semiconductor device, comprising the step of forming a protective film on the protruding electrode forming surface of a member with a protruding electrode using the energy ray curable resin film described in claim 1 or 2.
Citation Information
Patent Citations
Resin film, composite sheet and method for producing semiconductor device
WO2021172431A1